Sublethal tree health conditions suppress tree growth across eastern US forests - K. Diego Rocha; Lukas J. Magee; Denver T. Cayetano; D. Alex Bowers; Kristina J. Anderson-Teixeira; Sean M. McMahon; Jessica Shue; David A. Orwig; Stephanie Bohlman; Jason Vogel; Timothy A. Martin; William J. McShea; et al. (Forest Ecology and Management, 2026)

Reservoir characterization and petrophysical evaluation of Agbada formation sandstones in the “SAFA” field, Niger delta basin, Nigeria - Ifeyinwa Juliana Ofoh; Timothy Chibuike Anyanwu; Eze Martins Okoro; Chibuike Daniel Ibeh; Samuel Okechukwu Onyekuru (Journal of African Earth Sciences, 2026)

Impact of light intensity and tank color on growth and development of largemouth bass, Micropterus nigricans, during early life history - Anneleen Swanepoel; Nelson S. Parajuli; Kaylan Martin; Kyle R. Wood; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; Timothy J. Bruce; D. Allen Davis; Ian A.E. Butts (Aquaculture, 2026)

PFAS in Australian raptor species: terrestrial biomonitors of environmental contamination in changing ecosystems - Phoebe Lewis; Christopher P. Johnstone; Timothy Chaston; Jordan O. Hampton; Judy Clarke; John Leeder; Yan Wang; Matthew Etterson; Jennifer Martin; Minna Saaristo (Environmental Pollution, 2026)

Chronic nicotine vapor-induced enhancement of ethanol drinking-in-the-dark is associated with reduced medial prefrontal cortical activity - Timothy G. Freels; Jennifer Li; Rebecca G. Pavchinskiy; Rubing Zhao-Shea; Gilles E. Martin; Andrew R. Tapper (Psychopharmacology, 2026)

Spatial Genetic Structure and Diversity Reveal Central‐Marginal Patterns in the Rare Freshwater Mussel, Pleurobema riddellii - Alexander S. Zalmat; Matthew Harrison; Brad Littrell; Kyle T. Sullivan; Charles R. Randklev; Timothy H. Bonner; Noland H. Martin (Journal of Biogeography, 2026)
Aim This study sought to evaluate how historical drainage connectivity and contemporary basin isolation have shaped population genetic structure and diversity in an imperilled species of freshwater mussel, Pleurobema riddellii. Location Covers the range of P. riddellii , spanning seven river basins of the Gulf Coastal Plains of the southern USA, including the San Jacinto, Neches, Sabine, Calcasieu, Red, Ouachita and Pearl river systems. Methods A genome‐wide single nucleotide polymorphism (SNP) dataset was generated using a restriction‐site associated DNA sequencing approach. After filtering and assembly, a dataset consisting of 12,062 SNP loci from 351 individuals was retained. Population genetic structure was evaluated using principal components analysis and a Bayesian clustering model, ENTROPY. Genetic differentiation among river basins was quantified using Nei's G ST and patterns of genetic diversity were assessed using observed heterozygosity and Watterson's θ . Results Population genetic analyses revealed structuring that corresponded closely with river basin boundaries. Centrally distributed populations from the Neches, Sabine and Calcasieu basins formed a genetically cohesive group characterised by low genetic differentiation and elevated genetic diversity. Marginal populations from the San Jacinto, Red, Ouachita and Pearl basins exhibited higher levels of genetic differentiation and reduced genetic diversity. Main Conclusions Here, we demonstrate a central‐marginal pattern in genomic structure and diversity across the range of P. riddellii . These results suggest that historical hydrological connectivity, coupled with prolonged isolation and reduced effective population sizes at range margins, likely played a role in shaping standing genomic variation in this system. More broadly, the genomic structure observed in P. riddellii is consistent with other unionid mussels in the region, highlighting the contributions of historical hydrological configurations in structuring freshwater biodiversity.

Heterospecific social behavior in primates: insights into the evolutionary roots of pet-keeping - Cyril C. Grueter; Fany Roncin; K. Anne-Isola Nekaris; Jill Pruetz; Richard McFarland; Sabit Hasan; Malgorzata Arlet; Timothy M. Eppley; Susan M. Cheyne; Vincent Nijman; Eckhard W. Heymann; Pascal R. Marty; et al. (Primates, 2026)
Primate interspecific interactions with both other primates and non-primate species range from predator–prey dynamics to affiliative behaviors such as grooming, play, and carrying. While many primates participate in interspecific associations or commensal relationships, to our knowledge interspecific social interactions have never been systematically synthesized. Here, we present the first comprehensive review of such interactions, compiling 427 cases from the literature, media sources, and a global survey of primatologists. These involved 88 primate species and 127 non-primate species (including mammals, birds, reptiles, amphibians, malacostracans, and insects) across wild (n = 311) and captive (n = 111) contexts. The most frequent interactions occurred within or between primate families (e.g., Cercopithecidae–Cercopithecidae, Cebidae–Atelidae), though affiliative behaviors were also directed toward distantly related taxa such as dogs and birds. Play (n = 139) and grooming (n = 136) were most common. Juveniles and infants predominantly engaged in play, while adult females were more likely to groom. Adult males were less affiliative overall. Contrary to expectations, affiliative behaviors were not more often directed toward immature than adult heterospecifics. Primates were the initiators in most interactions. These findings offer new insights into the diversity and contexts of heterospecific sociality in primates and suggest that some behavioral tendencies relevant to later forms of human–animal companionship – such as caregiving, tolerance, and exploratory play – may be more widespread among primates than previously recognized.

The impact of isosmotic conditions on the metabolism and hypoxia tolerance of a reportedly oxyconforming teleost - Timothy D. Clark; Luis L. Kuchenmüller; Elizabeth C. Hoots; Maryane Gradito; Jake M. Martin (Journal of Fish Biology, 2026)
Fish must manage the competing demands of ion balance and gas exchange across the gills – a physiological tension known as the osmorespiratory compromise. In dynamic estuarine environments, the osmorespiratory compromise may be exacerbated by variable salinity and periods of hypoxia that demand high respiratory work. This study examined whether acute exposure to isosmotic conditions (9 ppt) lowers aerobic metabolism and enhances hypoxia tolerance relative to fresh water (0 ppt) in the fish Galaxias maculatus , a species that purportedly lacks oxyregulatory capacity when faced with hypoxia. Analysis via Bayesian mixed models found no impact of salinity on routine or standard oxygen uptake rates ( Ṁ O 2 ). The majority of fish maintained their Ṁ O 2 as oxygen declined to ~10% air saturation, with only 8 of 58 individuals displaying a measurable critical oxygen saturation (O 2crit ). Average O 2crit values were similar across treatments (25.3% in 0 ppt versus 24.3% in 9 ppt), though the small number of fish showing a clear threshold suggests that the average O 2crit of the species might be substantially lower. Contrary to earlier reports, our findings show that G. maculatus has an oxyregulatory capacity that aligns with other teleosts. The marked interindividual variability in Ṁ O 2 patterns with progressive hypoxia was a feature of this study when compared with other species, adding to a growing pattern of impressive physiological plasticity in G. maculatus . A clearer understanding of the consequences of the osmorespiratory compromise at the whole‐animal level relies on further examinations of the interplay between salinity and oxygen across stenohaline and euryhaline species and across acute and chronic exposures.

Faunal community ecology of central-eastern Indian Ocean Seamounts - Timothy D. O'Hara; Shane T. Ahyong; Phil Alderslade; Dianne Bray; Francesco Criscione; Niki Davey; Caroline Farrelly; Martin F. Gomon; Ana Hara; Jeremy Horowitz; Andrew M. Hosie; Lisa Kirkendale; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

A remarkably diverse proboscidean assemblage from Early Miocene Buluk, Kenya - William J. Sanders; Ellen R. Miller; Martin K. Muthuri; Timothy G. Ibui; Pauline M. Mbatha; Adam N. Rountrey; Isaiah O. Nengo (Journal of Mammalian Evolution, 2026)
The late Early Miocene site of Buluk, Kenya, has yielded a rich mammalian fauna comprised of about 30 species in 20 genera, notably including a stem cercopithecoid and a range of primitive hominoids. This temporal interval is poorly represented in Africa but is important because it coincides with the Miocene Climatic Optimum (MCO), a previous period of global warming tied to a carbon excursion. As the only late Early Miocene fossiliferous locality in eastern Africa that falls within the MCO, Buluk is of singular value to paleontological studies for increasing understanding of faunal responses to climate change and related ecological transformations. Paleobotanical, geochemical, and dental isotopic investigations indicate that Buluk was a C 3 -dominated woodland ecosystem with a strongly seasonal subhumid to subarid climate and overall greater rainfall than at present. Depositional circumstances are primarily channel fills associated with a large fluviatile system with water transport of vertebrates over a limited distance, probably denoting an autochthonous fauna. The most abundant large mammals in the fauna are proboscideans. Comparative morphological and metric study of the proboscidean assemblage reveals the co-occurrence of at least six genera and species from three higher taxa, Deinotheriidae and the elephantimorph families Mammutidae and Gomphotheriidae. Three of these species are new, one of them marking the earliest appearance of Protanancus . Deinotheres and archaeobelodonts are equally the most common proboscidean taxa in the assemblage. Such diversity of megaherbivores was not unusual for African Miocene sites and may have been accommodated by faunal differences from modern conditions, resource partitioning, and physical competitive displacement. The relatively diminutive size of molars of proboscideans in the assemblage, most pronounced among female elephantimorphs, may have constituted coordinated dwarfing in response to either increasing temperatures or stresses on resources caused by the MCO.

Contrasting life‐history strategies of three sympatric icefish species in the northern Scotia Sea - Huw W. James; Timothy Jones; Fabrice Stephenson; Philip R. Hollyman; William D. K. Reid; Martin A. Collins (Journal of Fish Biology, 2026)
Comprehending a species' life‐history strategies is crucial to inform effective conservation efforts. Commercial fishing impacts icefish (family: Channichthyidae) in the Scotia Sea, but detailed information on species‐specific life histories remains largely unknown. In this study, the demographic characteristics of mackerel icefish ( Champsocephalus gunnari ), blackfin icefish ( Chaenocephalus aceratus ) and South Georgia icefish ( Pseudochaenichthys georgianus ) were examined and used to compare inferred life‐history strategies, using long‐term data from demersal and plankton trawl surveys conducted across the South Georgia and the Shag Rocks continental shelves. The results indicated that C. gunnari may exhibit alternative reproductive tactics, as they appear to spawn multiple times in a single year and mature at varying sizes. Conversely, C. aceratus and P. georgianus reproduced once per annum and appeared to favour investing in somatic growth, resulting in them consistently maturing at a larger size. Seasonal sex ratios demonstrated a reduction in captured mature males for C. aceratus and P. georgianus during the suspected spawning period, supporting the hypothesis of sex‐specific behavioural patterns during the reproductive period. These findings highlight the variation in the life‐history strategies among these three icefish species, which should be considered during the development of future management measures.

Faith without action? Christian ecological conviction and the civic participation gap in Australia - Timothy J. Healy; Johannes M. Luetz; Martin J. Hodson (Ambio, 2026)
Three-quarters of the world’s population identify with a religion, suggesting that faith communities constitute a vast (yet under-mobilised) civic infrastructure for sustainability transitions. Christianity remains the world’s largest religious tradition, making it consequential for analysing conviction–action dynamics. Using Australia as a case study, this research investigates why widely professed moral concern for the environment does not translate more readily into collective environmental action. Using Australia as a case study, our national sample survey ( n = 1295), weighted to reflect the Australian population aged 18+, indicates a belief-action gap that is systematic rather than incidental, underpinned by barriers across micro-meso-macro levels. Our analysis identifies actionable strategies to help faith communities translate ecological conviction into effective civic engagement with policy-relevant sustainability outcomes. By clarifying pathways through which faith commitments can be mobilised into civic action, the article offers insights transferable beyond Australia and churches to other national and faith contexts, with implications for advancing SDGs 3, 6, 11, 12, 13, 16, and 17.

Hums in the humus: opportunities and challenges for soil ecoacoustics - Alex F. Taylor; Martin F. Breed; Carlos Abrahams; Amy Annells; Tom Bradfer-Lawrence; Timothy Cavagnaro; Carolyn-Monika Görres; Martin M. Gossner; Craig Liddicoat; Simon Linke; Oliver C. Metcalf; Louise Roberts; et al. (Trends in Ecology & Evolution, 2026)

Physicochemical and flavor profile characterization of sesame oils from different processing methods: Implications for quality control and market regulation - Yong Yang; Timothy J. Tse; Jinglun Zhou; Fengqin Tu; Huiwen Fang; Martin J.T. Reaney; Meiyu Zheng; Fenfen Lei; Li Zhou; Shu Wang (Food Chemistry, 2026)

Radiocarbon analysis reveals the contribution of aged terrestrial carbon to sedimentary methane cycling - Sigrid van Grinsven; Benedict V. A. Mittelbach; Fatemeh Ajallooeian; Thomas Laemmel; Martin Wessels; Negar Haghipour; Sönke Szidat; Timothy I. Eglinton; Zongguang Liu; Xiaojuan Feng; Carsten J. Schubert (Limnology and Oceanography, 2026)
Methane (CH 4 ) production in lacustrine sediments is known to be spatially heterogeneous, varying both horizontally and vertically. Porewater methane concentrations often differ between locations within a lake and with depth within the sediment profile. The drivers of this heterogeneity are often not well understood. Here, we explore methane cycling in the sediments of Lake Constance, the 2 nd largest perialpine lake in Europe, with well‐documented sedimentary methane production. We use a novel radiocarbon ( 14 C) based approach to determine the origin and age of buried carbon pools, as well as that of CO 2 and CH 4 in sediment porewaters at two locations with contrasting sediment supply, dominated by either allochthonous or autochthonous inputs. We show that porewater CO 2 is predominantly derived from inorganic carbon inputs, whereas CH 4 is produced from a mixture of CO 2 ‐derived and organic carbon‐derived substrates. At the allochthonous‐dominated location, a larger fraction of the CH 4 seemed to be produced from organic substrates than in the autochthonous location, where the 14 C signals of CO 2 and CH 4 were more comparable to one another. Furthermore, 14 C contents of lignin‐derived phenols and fatty acids, as proxies for mineral‐associated and free organic matter respectively, suggest that the “recalcitrant” carbon pool contributes to the methane production in centennial‐aged sediments. Microbial community data further suggest active methane production in these old sediments, challenging concepts of permanent organic carbon burial in deeper sediment layers and on the recalcitrance of the buried material.

Distribution and ecology of the four Macrourus species by‐caught in the longline fishery at South Georgia, Southern Ocean - José Abreu; Philip R. Hollyman; Jennifer J. Freer; M. L. Romero Martínez; José P. Queirós; Timothy Jones; Richard A. Phillips; José C. Xavier; Martin A. Collins (Journal of Fish Biology, 2026)
Although Macrourus species are the main by‐catch across Southern Ocean longline fisheries, including around South Georgia, the lack of species‐specific data has hindered effective management and ecological understanding. Aggregation of macrourids at genus level masks critical interspecific differences in life‐history strategies and vulnerabilities to fishing. Here, we provide the first comprehensive biological assessment of the four macrourid species caught in South Georgia waters: Macrourus caml , Macrourus carinatus , Macrourus holotrachys and Macrourus whitsoni . Using fishery and observer data collected in 2018–2022, we reveal pronounced female‐biased sex ratios in three species ( M. holotrachys , M. carinatus and M. caml ), strong depth‐based segregation by body length, distinct distributions and habitat preferences related to environmental features (bathymetric depth and slope, primary productivity and temperature). By‐catch rates were highest in the southern region of South Georgia and varied across species: M. holotrachys was the most frequently caught and had a wide spatial and bathymetric distribution (∼1000–1750 m); M. caml was the second most caught and appeared the most flexible in terms of habitat use; M. carinatus was mainly caught in the west, including at Shag Rocks; and M. whitsoni was caught less frequently and in deeper water (> 1500 m), mostly in the northeast and east, and had the most restricted distribution. These interspecific differences underscore the need for species‐level assessments of fisheries risk and improved data collection to fill knowledge gaps. Overall, this study provides a critical foundation for understanding the ecology of Macrourus species in sub‐Antarctic ecosystems and highlights that additional data are required for by‐caught species to aid species‐level management in toothfish longline fisheries in the CCAMLR area.

Perspectives On Circular Economy and Efficient Resource Utilization of Valorized Value-Added Material for Sustainable Development - Kingsley Igenepo John; Aderemi Timothy Adeleye; Sehrish Munsif; Babatope Oluseun Odusina; Martins O. Omorogie (Circular Economy and Sustainability, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Effect of short-term storage on sperm quality and microbiome dynamics in blue catfish, Ictalurus furcatus - Samitha S.N. Liyanage; Kasun A. Bandara; Kaylan A. Martin; Kyle R. Wood; Jason W. Abernathy; Benjamin H. Beck; Timothy J. Bruce; Luke A. Roy; Rex A. Dunham; Xu Wang; Ian A.E. Butts (Aquaculture, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Blowing the trumpet for fungal conservation: a comprehensive assessment of the conservation status of Cantharellus and Craterellus - James R. S. Westrip; Kelmer Martins-Cunha; Gregory M. Mueller; Elisandro Ricardo Drechsler-Santos; Timothy A. Liddle; Ibai Olariaga Ibarguren; Janet Scott; Christine Tansey; Aída M. Vasco-Palacios; Felipe Wartchow; Anders Dahlberg (Biodiversity and Conservation, 2026)
There is a growing appreciation of the role that fungi play in ecosystems, and thus their importance in conservation efforts. However, they remain under-represented and very few species have had their conservation status assessed at a global level. In this study we looked at a well-known group of fungi, the chanterelles of Cantharellus and Craterellus and evaluated the extinction risk of this group using the IUCN Red List methodology. While there was a high level of species assessed as Data Deficient, when compared to other comprehensively assessed taxonomic groups on the Red List, the proportion of species that fall within a threatened category, or as a species of conservation concern, is in the range of values for other groups. The threats driving such assessments are predominantly those that are driving habitat loss and deterioration, that would be impacting a suite of other species too. Thus, the conservation of fungi should be more readily streamlined with efforts for other taxonomic groups. The spatial distribution of chanterelle species of conservation concern broadly overlaps with ecoregions of known conservation importance but also highlights a new separate hotspot for fungal conservation, namely the Congo Basin; and given the importance of the Congo rainforest as the second largest after the Amazon, ensuring the maintenance of forest biodiversity through the conservation of such fungi is of critical importance.

Exploring lactic acid bacteria in food, human health, and agriculture - Reona Murata; Youn Young Shim; Young Jun Kim; Martin J. T. Reaney; Timothy J. Tse (Critical Reviews in Food Science and Nutrition, 2025)

Spatial and Temporal Variation in Wave Overtopping Across a Coastal Structure Based on One Year of Field Observations - Jennifer Brown; Gerd Masselink; Margaret Yelland; Christopher Stokes; Timothy Poate; Robin Pascal; David Jones; John Walk; Christopher Cardwell; Barry Martin; Peter Ganderton; Julie Gregory; et al. (Journal of Marine Science and Engineering, 2025)
Coastal managers worldwide must prepare for changes in annual wave overtopping events due to climate change and sea-level rise. Research often assesses overtopping discharges by extreme events at a sea wall crest, typically using data from physical models or empirical rules based on scaled experiments. Here, we analyse a unique 1-year field dataset of coastal wave overtopping, from SW England, to determine the number of individual waves, regardless of their size, overtopping two locations across a coastal structure. The coastal conditions causing the most frequent overtopping differ from those driving it landward, complicating hazard communications for multiuse infrastructure. These data are the first field observations covering a year of tide, wave and wind conditions that cause overtopping of a vertical sea wall. Storms have a minimal (

Prickly politics: How Rosa rubiginosa (Sweet-Briar Rose) divides rural communities, private landowners, and commercial players in South Africa - Grant D. Martin; Kim Canavan; Timothy Westwood; Gerald Chikowore; Gavin Fraser; Quinn Clark; Stephanie Payne; Sandy-Lynn Steenhuisen (South African Journal of Botany, 2025)

Comparing apples and apples; evaluating the impact of conventional and organic management on the soil microbial communities of apple orchards - Kate E. Matthews; Martin F. Breed; Erinne Stirling; Lynne M. Macdonald; Timothy R. Cavagnaro (Applied Soil Ecology, 2025)

Advanced polystyrene nanoplastic remediation through electro-Fenton process: Degradation mechanisms and pathways - Qian Ye; Hao Xu; Timothy N. Hunter; David Harbottle; Girish M. Kale; Martin R. Tillotson (Journal of Environmental Chemical Engineering, 2025)

Frying characteristics of beef tallow as a potential alternative for intermittent deep-fat frying - Fenfen Lei; Meiyu Zheng; Tianyu Zhang; Timothy J. Tse; Martin J.T. Reaney; Shu Wang; Xiaoming Jiang; Bin Li; Zhigang Hu; Dongping He; Sihong Zhang; Qinfeng Zhang; et al. (Food Chemistry, 2025)

Recent and Rapid Assembly of an Island Species–Area Relationship Threatened by Human Disturbance - Luiz Jardim de Queiroz; Timothy J. Alexander; Daniela Achleitner; Martin Luger; Hubert Gassner; Carmela J. Doenz; Soraya Villalba; Lukas Rüber; Rampal S. Etienne; Luis Valente; Ole Seehausen (Ecology Letters, 2025)
The island species–area relationship (ISAR) describes how larger islands support more species. ISARs of isolated oceanic archipelagos, assembled over millions of years, typically show positive relationships, steep slopes, and species richness equilibrium. However, it remains unclear how quickly such characteristics emerge. We compiled a dataset for fish communities of 79 postglacial peri‐Alpine lakes and report an ISAR, formed de novo in less than 15,000 years, that partially mirrors older systems, but has an asymptotic shape. Immigration and speciation, the main ISAR drivers, are primarily associated with area and depth, respectively. Immigration increases with area, while speciation is promoted by greater depth, likely due to species depletion in the source pool and ecological constraints on speciation. This young ISAR has been reshaped by anthropogenic activities, with species introductions erasing its asymptotic shape. We demonstrate that ISARs can develop rapidly after insular habitat formation, offering insights into patterns of biodiversity assembly.

HESI GTTC ring trial: Concordance between Ames and rodent carcinogenicity outcomes for N-nitrosamines (NAs) with rat and hamster metabolic conditions - Joel Bercu; Alejandra Trejo-Martin; Connie Chen; Maik Schuler; Jennifer Cheung; Tetyana Cheairs; Anthony M. Lynch; Dean Thomas; Andreas Czich; Aisar Atrakchi; Timothy J. McGovern; Robert H. Heflich; et al. (Regulatory Toxicology and Pharmacology, 2025)

Isolation and characterisation of Klebsiella pneumoniae bacteriophages vB_Kpn_Lilla1 and vB_Kpn_Lilla2 - Timothy Martin; Liana Theodoridis; Emma Stent; Julia Lilla; Steve Petrovski (Archives of Virology, 2025)
Klebsiella pneumoniae is an opportunistic pathogen that is commonly associated with pulmonary infections. It is of particular concern due to its increasing resistance to antibiotics, particularly carbapenem. Alternative treatments for these bacterial infections are required, and phage application is an attractive option. In this study, we isolated two novel Klebsiella pneumonia bacteriophages from wastewater, vB_Kpn_Lilla1 and vB_Kpn_Lilla2, both of which have lytic activity against Klebsiella oxytoca and Klebsiella michiganensis . Genome sequencing and phylogenetic analysis revealed that both phages belong to the family Straboviridae , with vB_Kpn_Lilla1 belonging to the genus Jiaodavirus and vB_Kpn_Lilla2 belonging to the genus Slopekvirus . Growth kinetics showed an effective reduction of K. pneumoniae populations when infected with either phage.

Do soil enzymes respond to silvicultural management? - Fernanda C.C. Oliveira; Allan Bacon; Thomas R. Fox; Eric J. Jokela; Michael B. Kane; Timothy A. Martin; Asko Noormets; C. Wade Ross; Jason Vogel; Daniel Markewitz (Forest Ecology and Management, 2025)

Chemical property, bioactive constituent and volatile compound changes of beef tallow during an improved flavor-retaining refining approach - Li Zhou; Meiyu Zheng; Tianyu Zhang; Shu Wang; Xiaoming Jiang; Bin Li; Zhigang Hu; Timothy J. Tse; Martin J.T. Reaney; Qiangsheng Nie; Dongping He; Chuanrong Hu; et al. (Food Chemistry, 2025)

Repeat duplication and divergence in the linusorb-related gene family in flax (Linum usitatissimum) - Ziliang Song; Timothy F. Sharbel; Yong Wang; Martin J.T. Reaney (Food Bioscience, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Phylogenomic insights into the taxonomy, ecology, and mating systems of the lorchel family Discinaceae (Pezizales, Ascomycota) - Alden C. Dirks; Andrew S. Methven; Andrew N. Miller; Michelle Orozco-Quime; Sundy Maurice; Gregory Bonito; Judson Van Wyk; Steven Ahrendt; Alan Kuo; William Andreopoulos; Robert Riley; Anna Lipzen; et al. (Molecular Phylogenetics and Evolution, 2025)

Hydrogeological implications of fault-related folding in a Triassic braided sandstone - Timothy C. McMillan; Titus Murray; Martin S. Andersen; Wendy A. Timms; Gabriel C. Rau (Journal of Structural Geology, 2025)

Pre‐aged organic matter dominates organic carbon burial in a major perialpine lake system - Benedict V. A. Mittelbach; Alexander S. Brunmayr; Margot E. White; Timo M. Y. Rhyner; Negar Haghipour; Thomas M. Blattmann; Martin Wessels; Nathalie Dubois; Timothy I. Eglinton (Limnology and Oceanography, 2025)
Organic carbon (OC) burial in lake sediments is comparable to that in marine sediments globally. However, climatic and carbon cycle implications depend on the origin of buried OC. This study utilizes high‐resolution radiocarbon ( 14 C) measurements in combination with stable carbon isotopes ( 13 C) and total organic carbon/total nitrogen ratios to constrain sources and ages of OC deposited since the early 20 th century in Lake Constance, the second‐largest lake in central Europe. We differentiate between aquatic, pre‐aged soil, and fossil rock‐derived (petrogenic) OC. The shape and magnitude of the 14 C bomb spike recorded in the sediment profile indicate the sequestration of recently synthesized biospheric OC with a complex overlay from different OC sources. We find that soil‐derived OC is the dominant component of sedimentary OC, with a mean transit time in the catchment of around 110 yr. Additionally, we quantified the 14 C dynamics of dissolved inorganic carbon in the lake, which can be modeled with a mean transit time of around 10 yr. An ordinary kriging spatial analysis revealed that the Alpine Rhine delta and the profundal areas are the primary loci for allochthonous OC deposition. Lake‐wide surface sediment OC fluxes were spatially heterogeneous but averaged 52.0 gC m −2 yr −1 , where 26.7 gC m −2 yr −1 of mostly stable, allochthonous OC are buried long term. This study highlights the necessity of accounting for both pre‐aged and fossil OC sources, as well as spatial heterogeneity, when assessing the response of lakes and, more broadly, source‐to‐sink systems to ongoing climate and ecosystem change.

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Antibiotic residues and antibiotic resistance genes in African water systems: Implications for safe drinking water, aquatic ecosystems, and Sustainable Development Goals - Emmanuel Sunday Okeke; Chidiebele Emmanuel Ikechukwu Nwankwo; Timothy Prince Chidike Ezeorba; Martins Obinna Ogugofor; Charles Ogugua Nwuche (Journal of Water Process Engineering, 2025)

Carbon recovery in secondary forests: Insights from three West African countries - Paly N. Titenwi; Moses N. Sainge; Usif Kargbo; Richard A.S. Kamara; Alex Musa; Timothy M. Kabba; Bockarie K. Buanie; Andre L. Njouonkou; Edward Aruna; Martin J.P. Sullivan; Ana Leite; Aida Cuni-Sanchez (Forest Ecology and Management, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Electrostatic field as an emergent technology in refining crude oils: a review - Li Zhou; Timothy J. Tse; Farley Chicilo; Venkatesh Meda; Martin J. T. Reaney (Critical Reviews in Food Science and Nutrition, 2024)

Environmental Change Drivers Reduce Sapling Layer Diversity in Sugar Maple-Beech Forests of Eastern North America - Michael R. Zarfos; Gregory B. Lawrence; Colin M. Beier; Blair D. Page; Todd C. McDonnell; Timothy J. Sullivan; Mariann T. Garrison-Johnston; Martin Dovciak (Ecosystems, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Mechanisms underlying reproductive responses of Japanese quails to heat stress conditions - Ifeanyichukwu Chukwuemeka Egbuniwe; Martins Steven Akogwu; Timothy Ugochukwu Obetta (International Journal of Biometeorology, 2024)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Photocatalytic treatment of diverse contaminants of potential concern in oil sands process-affected water - Jeffrey T. Martin; Timothy M.C. Leshuk; Kieran Armstrong; Tia Chai; Zachary W. Young; Theo Paradis; Asfaw Bekele; Todd White; Frank Gu (Chemosphere, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The last days of Aporia crataegi (L.) in Britain: Evaluating genomic erosion in an extirpated butterfly - Rebecca Whitla; Korneel Hens; James Hogan; Geoff Martin; Casper Breuker; Timothy G. Shreeve; Saad Arif (Molecular Ecology, 2024)
Current rates of habitat degradation and climate change are causing unprecedented declines in global biodiversity. Studies on vertebrates highlight how conservation genomics can be effective in identifying and managing threatened populations, but it is unclear how vertebrate‐derived metrics of genomic erosion translate to invertebrates, with their markedly different population sizes and life histories. The Black‐veined White butterfly ( Aporia crataegi ) was extirpated from Britain in the 1920s. Here, we sequenced historical DNA from 17 specimens collected between 1854 and 1924 to reconstruct demography and compare levels of genomic erosion between extirpated British and extant European mainland populations. We contrast these results using modern samples of the Common Blue butterfly ( Polyommatus icarus ); a species with relatively stable demographic trends in Great Britain. We provide evidence for bottlenecks in both these species around the period of post‐glacial colonization of the British Isles. Our results reveal different demographic histories and N e for both species, consistent with their fates in Britain, likely driven by differences in life history, ecology and genome size. Despite a difference, by an order of magnitude, in historical effective population sizes ( N e ), reduction in genome‐wide heterozygosity in A. crataegi was comparable to that in P. icarus . Symptomatic of A. crataegi 's disappearance were marked increases in runs‐of‐homozygosity (RoH), potentially indicative of recent inbreeding, and accumulation of putatively mildly and weakly deleterious variants. Our results provide a rare glimpse of genomic erosion in a regionally extinct insect and support the potential use of genomic erosion metrics in identifying invertebrate populations or species in decline.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes - Craig Liddicoat; Robert A. Edwards; Michael Roach; Jake M. Robinson; Kiri Joy Wallace; Andrew D. Barnes; Joel Brame; Anna Heintz-Buschart; Timothy R. Cavagnaro; Elizabeth A. Dinsdale; Michael P. Doane; Nico Eisenhauer; et al. (Science of The Total Environment, 2024)

Tissue elements in co-occurring herbs scale mostly isometrically, but do different plant strategies play the same game? - Martin Bitomský; Timothy Harris; Jitka Klimešová (Plant and Soil, 2024)

Challenges in assessing and managing multi-hazard risks: A European stakeholders perspective - Robert Šakić Trogrlić; Karina Reiter; Roxana L. Ciurean; Stefania Gottardo; Silvia Torresan; Anne Sophie Daloz; Lin Ma; Noemi Padrón Fumero; Sharon Tatman; Stefan Hochrainer-Stigler; Marleen C. de Ruiter; Julius Schlumberger; et al. (Environmental Science & Policy, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

A review of flaxseed lignan and the extraction and refinement of secoisolariciresinol diglucoside - Yingxue Hu; Timothy J. Tse; Youn Young Shim; Sarah K. Purdy; Young Jun Kim; Venkatesh Meda; Martin J. T. Reaney (Critical Reviews in Food Science and Nutrition, 2024)

Chemical effects on neural network activity: Comparison of acute versus network formation exposure in microelectrode array assays - Melissa M. Martin; Amy F. Carpenter; Timothy J. Shafer; Katie Paul Friedman; Kelly E. Carstens (Toxicology, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Source mechanism of kHz microseismic events recorded in multiple boreholes at the first EGS Collab testbed - Yan Qin; Jiaxuan Li; Lianjie Huang; Martin Schoenball; Jonathan Ajo-Franklin; Douglas Blankenship; Timothy J. Kneafsey (Geothermics, 2024)

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Large-Scale Laboratory Testing of Helical Piles: Effect of the Shape - Abdullah M. A. Al-Rawabdeh; Jayan S. Vinod; Martin D. Liu; Timothy J. McCarthy; Scott Redwood (Geotechnical and Geological Engineering, 2024)

Increased abundance of potentially pathogenic Vibrio and a marine heatwave co-occur with a Pacific Oyster summer mortality event - Nachshon Siboni; William L. King; Nathan L.R. Williams; Elliot Scanes; Marco Giardina; Timothy J. Green; Martin Ostrowski; Wayne O'Connor; Michael Dove; Maurizio Labbate; Justin R. Seymour (Aquaculture, 2024)

Movement dynamics and habitat selection of Suwannee bass Micropterus notius - Joel W. Yeager; Timothy F. Bonvechio; Martin J. Hamel (Hydrobiologia, 2024)

Adsorption and removal of polystyrene nanoplastics from water by green-engineered clays - Meichen Wang; Kendall Lilly; Leisha M.A. Martin; Wei Xu; Phanourios Tamamis; Timothy D. Phillips (Water Research, 2024)

Experimental demonstration of the heat transfer — pressure drop trade-off in 3D printed baffled logpile structures - Leon R.S. Rosseau; Timothy van Lanen; Ivo Roghair; Martin van Sint Annaland (Chemical Engineering Journal, 2024)

Quantifying conditions required for varve formation in meromictic Crawford Lake, Ontario, Canada: important process for delimiting the Anthropocene epoch - Brendan M. Llew-Williams; Francine M. G. McCarthy; Andrea M. Krueger; Nicholas L. Riddick; Michael D. MacKinnon; Krysten M. Lafond; R. Timothy Patterson; Nawaf A. Nasser; Martin J. Head; Michael F. J. Pisaric; Kevin W. Turner; Joseph I. Boyce; et al. (Journal of Paleolimnology, 2024)

Dynamic human, oceanographic, and ecological factors mediate transboundary fishery overlap across the Pacific high seas - Timothy H. Frawley; Barbara Muhling; Stephanie Brodie; Hannah Blondin; Heather Welch; Martin C. Arostegui; Steven J. Bograd; Camrin D. Braun; Megan A. Cimino; Nima Farchadi; Elliott L. Hazen; Desiree Tommasi; et al. (Fish and Fisheries, 2024)
The management and conservation of tuna and other transboundary marine species have to date been limited by an incomplete understanding of the oceanographic, ecological and socioeconomic factors mediating fishery overlap and interactions, and how these factors vary across expansive, open ocean habitats. Despite advances in fisheries monitoring and biologging technology, few attempts have been made to conduct integrated ecological analyses at basin scales relevant to pelagic fisheries and the highly migratory species they target. Here, we use vessel tracking data, archival tags, observer records, and machine learning to examine inter‐ and intra‐annual variability in fisheries overlap (2013–2020) of five pelagic longline fishing fleets with North Pacific albacore tuna ( Thunnus alalunga , Scombridae). Although progressive declines in catch and biomass have been observed over the past several decades, the North Pacific albacore is one of the only Pacific tuna stocks primarily targeted by pelagic longlines not currently listed as overfished or experiencing overfishing. We find that fishery overlap varies significantly across time and space as mediated by (1) differences in habitat preferences between juvenile and adult albacore; (2) variation of oceanographic features known to aggregate pelagic biomass; and (3) the different spatial niches targeted by shallow‐set and deep‐set longline fishing gear. These findings may have significant implications for stock assessment in this and other transboundary fishery systems, particularly the reliance on fishery‐dependent data to index abundance. Indeed, we argue that additional consideration of how overlap, catchability, and size selectivity parameters vary over time and space may be required to ensure the development of robust, equitable, and climate‐resilient harvest control rules.

Diagnosis of canine intestinal parasites: Improved detection of Dipylidium caninum infection through coproantigen testing - Susan Little; Jennifer Braff; Kathryn Duncan; David Elsemore; Rita Hanna; Jancy Hanscom; Alice Lee; Katy A. Martin; Caroline Sobotyk; Lindsay Starkey; Kellee Sundstrom; Phyllis Tyrrell; et al. (Veterinary Parasitology, 2023)

Recent strategies for the remediation of Ivermectin from the environment: A critical review - Aderemi Timothy Adeleye; Kingsley Igenepo John; Brigitte Helmreich; Martins O. Omorogie (Journal of Water Process Engineering, 2023)

Availability of bioactive flax lignan from foods and supplements - Timothy J. Tse; Yajia Guo; Youn Young Shim; Sarah K. Purdy; Ji Hye Kim; Jae Youl Cho; Jane Alcorn; Martin J. T. Reaney (Critical Reviews in Food Science and Nutrition, 2023)

Two decades of carbon dynamics in an actively-managed, naturally-regenerated longleaf/slash pine forest - Rosvel Bracho; Timothy A. Martin; Jason G. Vogel; Wendell P. Cropper Jr; Gerardo Celis; Kenneth Clark; Henry L. Gholz; Gregory Gorman; Henry W. Loescher; Thomas L. Powell; Scott Sager; Maryada Shrestha; et al. (Forest Ecology and Management, 2023)

Hydrology drives export and composition of carbon in a pristine tropical river - Travis W. Drake; Matti Barthel; Christian Ekemba Mbongo; Davin Mata Mpambi; Simon Baumgartner; Clement Ikene Botefa; Marijn Bauters; Martin R. Kurek; Robert G. M. Spencer; Amy M. McKenna; Negar Haghipour; Godé Lompoko Ekamba; et al. (Limnology and Oceanography, 2023)
The Ruki is a pristine blackwater tributary in the Congo Basin draining tropical lowland forest. Daily discharge and fortnightly concentrations, isotopic ratios, and molecular composition of carbon and organic matter were measured for 1 yr (2019–2020). Like the Congo River, discharge peaked from November–January, with a smaller secondary peak in June. Dissolved organic carbon (DOC), inorganic carbon (DIC), carbon dioxide ( p CO 2 ), and methane ( p CH 4 ) concentrations were high (21.3 ± 4.8 mg C L −1 , 5.8 ± 0.9 mg C L −1 , 6370 ± 1740 ppm, and 250 ± 100 ppm, respectively) and positively correlated with discharge, indicating transport limitation. Total suspended solids and particulate organic carbon (POC) concentrations were generally low (3.68 ± 1.61 mg L −1 , 0.88 ± 0.33 mg C L −1 , respectively) and varied inversely with discharge, indicating source limitation. The Ruki exported a total of 3.25 Tg C yr −1 , of which DOC, DIC, and POC comprised 76%, 20%, and 3%, respectively. This DOC flux represents ~ 20% of the annual Congo Basin flux from about 5% of its area, highlighting the high yield. Isotopic ratios of DOC and POC indicate modern C3 forest vegetation as a source, except for a few older samples potentially indicating peat inputs. The bulk molecular composition of dissolved organic matter was seasonally consistent; however, a more oxidized and aromatic assemblage occurred at high discharge, corresponding with forest vegetation, while a more aliphatic, nitrogen‐, and sulfur‐enriched assemblage was found during low discharge, corresponding with soil‐derived organic matter. Overall, these results underscore how hydrology controls C concentrations in the Ruki River and how this blackwater river contributes disproportionately to C export per unit area within the Congo Basin hydrosystem.

Hydraulic variability of tropical forests is largely independent of water availability - Chris M. Smith‐Martin; Robert Muscarella; William M. Hammond; Steven Jansen; Timothy J. Brodribb; Brendan Choat; Daniel M. Johnson; German Vargas‐G; María Uriarte (Ecology Letters, 2023)
Tropical rainforest woody plants have been thought to have uniformly low resistance to hydraulic failure and to function near the edge of their hydraulic safety margin (HSM), making these ecosystems vulnerable to drought; however, this may not be the case. Using data collected at 30 tropical forest sites for three key traits associated with drought tolerance, we show that site‐level hydraulic diversity of leaf turgor loss point, resistance to embolism (P 50 ), and HSMs is high across tropical forests and largely independent of water availability. Species with high HSMs (>1 MPa) and low P 50 values (

Soil biotic and abiotic thresholds in sugar maple and American beech seedling establishment in forests of the northeastern United States - Jordon C. Tourville; Michael R. Zarfos; Gregory B. Lawrence; Todd C. McDonnell; Timothy J. Sullivan; Martin Dovčiak (Plant and Soil, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Assessing the effectiveness of portable HEPA air cleaners for reducing particulate matter exposure in King County, Washington homeless shelters: Implications for community congregate settings - Ching-Hsuan Huang; Thu Bui; Daniel Hwang; Jeffry Shirai; Elena Austin; Martin Cohen; Timothy Gould; Timothy Larson; Igor Novosselov; Shirlee Tan; Julie Fox; Edmund Seto (Science of The Total Environment, 2023)

Measurements of sound propagation in Mars' lower atmosphere - Baptiste Chide; Xavier Jacob; Andi Petculescu; Ralph D. Lorenz; Sylvestre Maurice; Fabian Seel; Susanne Schröder; Roger C. Wiens; Martin Gillier; Naomi Murdoch; Nina L. Lanza; Tanguy Bertrand; et al. (Earth and Planetary Science Letters, 2023)

Applying genomics in regulatory toxicology: a report of the ECETOC workshop on omics threshold on non-adversity - Timothy W. Gant; Scott S. Auerbach; Martin Von Bergen; Mounir Bouhifd; Philip A. Botham; Florian Caiment; Richard A. Currie; Joshua Harrill; Kamin Johnson; Dongying Li; David Rouquie; Ben van Ravenzwaay; et al. (Archives of Toxicology, 2023)
In a joint effort involving scientists from academia, industry and regulatory agencies, ECETOC’s activities in Omics have led to conceptual proposals for: (1) A framework that assures data quality for reporting and inclusion of Omics data in regulatory assessments; and (2) an approach to robustly quantify these data, prior to interpretation for regulatory use. In continuation of these activities this workshop explored and identified areas of need to facilitate robust interpretation of such data in the context of deriving points of departure (POD) for risk assessment and determining an adverse change from normal variation. ECETOC was amongst the first to systematically explore the application of Omics methods, now incorporated into the group of methods known as New Approach Methodologies (NAMs), to regulatory toxicology. This support has been in the form of both projects (primarily with CEFIC/LRI) and workshops. Outputs have led to projects included in the workplan of the Extended Advisory Group on Molecular Screening and Toxicogenomics (EAGMST) group of the Organisation for Economic Co-operation and Development (OECD) and to the drafting of OECD Guidance Documents for Omics data reporting, with potentially more to follow on data transformation and interpretation. The current workshop was the last in a series of technical methods development workshops, with a sub-focus on the derivation of a POD from Omics data. Workshop presentations demonstrated that Omics data developed within robust frameworks for both scientific data generation and analysis can be used to derive a POD. The issue of noise in the data was discussed as an important consideration for identifying robust Omics changes and deriving a POD. Such variability or “noise” can comprise technical or biological variation within a dataset and should clearly be distinguished from homeostatic responses. Adverse outcome pathways (AOPs) were considered a useful framework on which to assemble Omics methods, and a number of case examples were presented in illustration of this point. What is apparent is that high dimension data will always be subject to varying processing pipelines and hence interpretation, depending on the context they are used in. Yet, they can provide valuable input for regulatory toxicology, with the pre-condition being robust methods for the collection and processing of data together with a comprehensive description how the data were interpreted, and conclusions reached.

PFAS soil concentrations surrounding a hazardous waste incinerator in East Liverpool, Ohio, an environmental justice community - Kaitlin Vollet Martin; Timothy J. Hilbert; Michael Reilly; W. Jay Christian; Anna Hoover; Kelly G. Pennell; Qunxing Ding; Erin N. Haynes (Environmental Science and Pollution Research, 2023)

Research priorities for the sustainability of coral-rich western Pacific seascapes - Graeme S. Cumming; Maja Adamska; Michele L. Barnes; Jon Barnett; David R. Bellwood; Joshua E. Cinner; Philippa J. Cohen; Jennifer M. Donelson; Katharina Fabricius; R. Quentin Grafton; Alana Grech; Georgina G. Gurney; et al. (Regional Environmental Change, 2023)
Nearly a billion people depend on tropical seascapes. The need to ensure sustainable use of these vital areas is recognised, as one of 17 policy commitments made by world leaders, in Sustainable Development Goal (SDG) 14 (‘Life below Water’) of the United Nations. SDG 14 seeks to secure marine sustainability by 2030. In a time of increasing social-ecological unpredictability and risk, scientists and policymakers working towards SDG 14 in the Asia–Pacific region need to know: (1) How are seascapes changing? (2) What can global society do about these changes? and (3) How can science and society together achieve sustainable seascape futures? Through a horizon scan, we identified nine emerging research priorities that clarify potential research contributions to marine sustainability in locations with high coral reef abundance. They include research on seascape geological and biological evolution and adaptation; elucidating drivers and mechanisms of change; understanding how seascape functions and services are produced, and how people depend on them; costs, benefits, and trade-offs to people in changing seascapes; improving seascape technologies and practices; learning to govern and manage seascapes for all; sustainable use, justice, and human well-being; bridging communities and epistemologies for innovative, equitable, and scale-crossing solutions; and informing resilient seascape futures through modelling and synthesis. Researchers can contribute to the sustainability of tropical seascapes by co-developing transdisciplinary understandings of people and ecosystems, emphasising the importance of equity and justice, and improving knowledge of key cross-scale and cross-level processes, feedbacks, and thresholds.

Heritage genetics for adaptation to marginal soils in barley - Sidsel Birkelund Schmidt; Lawrie K. Brown; Allan Booth; John Wishart; Pete E. Hedley; Peter Martin; Søren Husted; Timothy S. George; Joanne Russell (Trends in Plant Science, 2023)

An observing campaign to search for meteoroids of Bennu at Earth - Peter Jenniskens; Dante S. Lauretta; Lindsey R. Koelbel; Martin C. Towner; Phil Bland; Steve Heathcote; Timothy M.C. Abbott; Emmanuel Jehin; Toni Hanke; Elise Fahl; Rynault van Wyk; Tim Cooper; et al. (Icarus, 2023)

Genome-wide identification and functional prediction of silicon (Si) transporters in poplar (Populus trichocarpa) - Md Mahmudul Hassan; Samir Martin; Kai Feng; Timothy B. Yates; Guoliang Yuan; Madhavi Z. Martin; Stanton Martin; Wellington Muchero; Natalie A. Griffiths; David J. Weston; Xiaohan Yang (Plant Biotechnology Reports, 2023)
Silicon (Si) enhances plant tolerance to various biotic and abiotic stressors such as salinity, drought, and heat. In addition, Si can be biomineralized within plants to form organic carbon-containing phytoliths that can have ecosystem-level consequences by contributing to long-term carbon sequestration. Si is taken up and transported in plants via different transporter proteins such as influx transporters (e.g., Lsi1, Lsi6) and efflux transporters (e.g., Lsi2). Additionally, the imported Si can be deposited in plant leaves via silicification process using the Siliplant 1 (e.g., Slp1) protein. Functional homologs of these proteins have been reported in different food crops. Here, we performed a genome-wide analysis to identify different Si transporters and Slp1 homologs in the bioenergy crop poplar ( Populus trichocarpa Torr. and A. Gray ex W. Hook). We identified one channel-type Si influx transporter (PtLsi1; Potri.017G083300), one Si efflux transporter (PtLsi2; Potri.012G144000) and two proteins like Slp1 (PtSlp1a; Potri.004G168600 and PtSlp1b; Potri.009G129900 ) in the P. trichocarpa genome. We found a unique sequence (KPKPPVFKPPPVPI) in PtSlp1a which is repeated six times. Repeated presence of this sequence in PtSlp1a indicates that this protein might be important for silicification processes in P. trichocarpa. The mutation profiles of different Si transporters in a P. trichocarpa genome-wide association study population identified significant and impactful mutations in Potri.004G168600 and Potri.009G129900 . Using a publically accessible database ( http://bar.utoronto.ca/eplant_poplar/ ), digital expression analysis of the putative Si transporters in P. trichocarpa found low to moderate expression in the anticipated tissues, such as roots and leaves. Subcellular localization analysis found that PtLsi1/PtLsi2 are localized in the plasma membrane, whereas PtSlp1a/PtSlp1b are found in the extracellular spaces. Protein–Protein interaction analysis of PtLsi1/PtLsi2 identified Delta-1-pyrroline-5-carboxylate synthase (P5CS) as one of the main interacting partners of PtLsi2, which plays a key role in proline biosynthesis. Proline is a well-known participant in biotic and abiotic stress tolerance in plants. These findings will reinforce future efforts to modify Si accumulation for enhancing plant stress tolerance and carbon sequestration in poplar.

Intertidal biodiversity and physical habitat complexity on historic masonry walls: A comparison with modern concrete infrastructure and natural rocky cliffs - Timothy Baxter; Martin Coombes; Heather Viles (Marine Pollution Bulletin, 2023)

Estimation of survey efficiency and biomass for commercially important species from industry-based paired gear experiments - Timothy J. Miller; David E. Richardson; Philip J. Politis; Christopher D. Roebuck; John P. Manderson; Michael H. Martin; Andrew W. Jones (Fisheries Research, 2023)

Depletion of cyanogenic glycosides in whole flaxseed via Lactobacillaceae fermentation - Chao Huang; Timothy J. Tse; Sarah K. Purdy; Farley Chicilo; Jianheng Shen; Venkatesh Meda; Martin J.T. Reaney (Food Chemistry, 2023)

Balancing disturbance risk and ecosystem service provisioning in Swiss mountain forests: an increasing challenge under climate change - Timothy Thrippleton; Christian Temperli; Frank Krumm; Reinhard Mey; Jürgen Zell; Sophie Stroheker; Martin M. Gossner; Peter Bebi; Esther Thürig; Janine Schweier (Regional Environmental Change, 2023)
Climate change severely affects mountain forests and their ecosystem services, e.g., by altering disturbance regimes. Increasing timber harvest (INC) via a close-to-nature forestry may offer a mitigation strategy to reduce disturbance predisposition. However, little is known about the efficiency of this strategy at the scale of forest enterprises and potential trade-offs with biodiversity and ecosystem services (BES). We applied a decision support system which accounts for disturbance predisposition and BES indicators to evaluate the effect of different harvest intensities and climate change scenarios on windthrow and bark beetle predisposition in a mountain forest enterprise in Switzerland. Simulations were carried out from 2010 to 2100 under historic climate and climate change scenarios (RCP4.5, RCP8.5). In terms of BES, biodiversity (structural and tree species diversity, deadwood amount) as well as timber production, recreation (visual attractiveness), carbon sequestration, and protection against gravitational hazards (rockfall, avalanche and landslides) were assessed. The INC strategy reduced disturbance predisposition to windthrow and bark beetles. However, the mitigation potential for bark beetle disturbance was relatively small (− 2.4%) compared to the opposite effect of climate change (+ 14% for RCP8.5). Besides, the INC strategy increased the share of broadleaved species and resulted in a synergy with recreation and timber production, and a trade-off with carbon sequestration and protection function. Our approach emphasized the disproportionally higher disturbance predisposition under the RCP8.5 climate change scenario, which may threaten currently unaffected mountain forests. Decision support systems accounting for climate change, disturbance predisposition, and BES can help coping with such complex planning situations.

Endoplasmic Reticulum Stress-Regulated Chaperones as a Serum Biomarker Panel for Parkinson’s Disease - Katarzyna Mnich; Shirin Moghaddam; Patrick Browne; Timothy Counihan; Stephen P. Fitzgerald; Kenneth Martin; Ciaran Richardson; Afshin Samali; Adrienne M. Gorman (Molecular Neurobiology, 2023)
Examination of post-mortem brain tissues has previously revealed a strong association between Parkinson’s disease (PD) pathophysiology and endoplasmic reticulum (ER) stress. Evidence in the literature regarding the circulation of ER stress-regulated factors released from neurons provides a rationale for investigating ER stress biomarkers in the blood to aid diagnosis of PD. The levels of ER stress-regulated proteins in serum collected from 29 PD patients and 24 non-PD controls were measured using enzyme-linked immunosorbent assays. A panel of four biomarkers, protein disulfide-isomerase A1, protein disulfide-isomerase A3, mesencephalic astrocyte-derived neurotrophic factor, and clusterin, together with age and gender had higher ability (area under the curve 0.64, sensitivity 66%, specificity 57%) and net benefit to discriminate PD patients from the non-PD group compared with other analyzed models. Addition of oligomeric and total α-synuclein to the model did not improve the diagnostic power of the biomarker panel. We provide evidence that ER stress-regulated proteins merit further investigation for their potential as diagnostic biomarkers of PD. Graphical Abstract

Climatic controls on the survival and loss of ancient types of barley on North Atlantic Islands - Peter Martin; Terence A. Brown; Timothy S. George; Björn Gunnarson; Neil J. Loader; Paul Ross; John Wishart; Rob Wilson (Climatic Change, 2023)
For ancient types of barley at sites in the Scottish Isles, Faroes, and Iceland, we calculated minimum temperature requirements for grain production (grain production threshold, GPT) as accumulated degree days over the cropping season. Site suitability for barley from AD 1200 to 2000 was investigated by comparing these thresholds with reconstructions of annual cropping season degree days (CSDD) using temperature and tree-ring data. In Iceland, between AD 1200 and 1500, reconstructed CSDD were more favorable in the southwest (Reykjavik), with fewer years below the GPT, than in the North, East and West, but there were two periods (1340–1389 and 1426–1475) with low average CSDD and several years below the GPT which possibly influenced the abandonment of barley cultivation around this time. Reconstructed CSDD for the Faroes (Tórshavn) had only one year below the GPT, but 15 periods of four or more consecutive years with low CSDD which would have challenged barley cultivation, especially in the thirteenth century. Reconstructed CSDD were highest for the Scottish Isles, allowing a more prominent role of barley in the farming system and economy. Nevertheless, years with poor harvests or famines were common and about half were associated with low CSDD, resulting in a significant temperature link but also demonstrating the important contribution of other factors. Despite frequent unfavorable years in both the Faroes and Scottish Isles, resilient production systems, well-adapted barley strains and socio-economic factors allowed barley cultivation to continue, and some ancient types to survive to the present day.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Symbiotic ant traits produce differential host‐plant carbon and water dynamics in a multi‐species mutualism - Patrick D. Milligan; Timothy A. Martin; Elizabeth G. Pringle; Kirsten M. Prior; Todd M. Palmer (Ecology, 2023)
Cooperative interactions may frequently be reinforced by “partner fidelity feedback,” in which high‐ or low‐quality partners drive positive feedbacks with high or low benefits for the host, respectively. Benefits of plant–animal mutualisms for plants have been quantified almost universally in terms of growth or reproduction, but these are only two of many sinks to which a host‐plant allocates its resources. By investigating how partners to host‐plants impact two fundamental plant resources, carbon and water, we can better characterize plant–partner fidelity and understand how plant–partner mutualisms may be modulated by resource dynamics. In Laikipia, Kenya, four ant species compete for Acacia drepanolobium host‐plants. These ants differ in multiple traits, from nectar consumption to host‐plant protection. Using a 5‐year ant removal experiment, we compared carbon fixation, leaf water status, and stem non‐structural carbohydrate concentrations for adult ant–plants with and without ant partners. Removal treatments showed that the ants differentially mediate tree carbon and/or water resources. All three ant species known to be aggressive against herbivores were linked to benefits for host‐plant resources, but only the two species that defend but do not prune the host, Crematogaster mimosae and Tetraponera penzigi , increased tree carbon fixation. Of these two species, only the nectivore C. mimosae increased tree simple sugars. Crematogaster nigriceps , which defends the tree but also castrates flowers and prunes meristems, was linked only to lower tree water stress approximated by pre‐dawn leaf water potential. In contrast to those defensive ants, Crematogaster sjostedti , a poor defender that displaces other ants, was linked to lower tree carbon fixation. Comparing the effects of the four ant species across control trees suggests that differential ant occupancy drives substantial differences in carbon and water supply among host trees. Our results highlight that ant partners can positively or negatively impact carbon and/or water relations for their host‐plant, and we discuss the likelihood that carbon‐ and water‐related partner fidelity feedback loops occur across ant–plant mutualisms.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The serotonin receptor 3E variant is a risk factor for female IBS-D - Nikola Fritz; Sabrina Berens; Yuanjun Dong; Cristina Martínez; Stefanie Schmitteckert; Lesley A. Houghton; Miriam Goebel-Stengel; Verena Wahl; Maria Kabisch; Dorothea Götze; Mauro D’Amato; Tenghao Zheng; et al. (Journal of Molecular Medicine, 2022)
Irritable bowel syndrome (IBS) is a gut-brain disorder of multifactorial origin. Evidence of disturbed serotonergic function in IBS accumulated for the 5-HT 3 receptor family. 5-HT 3 Rs are encoded by HTR3 genes and control GI function, and peristalsis and secretion, in particular. Moreover, 5-HT 3 R antagonists are beneficial in the treatment of diarrhea predominant IBS (IBS-D). We previously reported on functionally relevant SNPs in HTR3A c.-42C > T (rs1062613), HTR3C p.N163K (rs6766410), and HTR3E c.*76G > A (rs56109847 = rs62625044) being associated with IBS-D, and the HTR3B variant p.Y129S (rs1176744) was also described within the context of IBS. We performed a multi-center study to validate previous results and provide further evidence for the relevance of HTR3 genes in IBS pathogenesis. Therefore, genotype data of 2682 IBS patients and 9650 controls from 14 cohorts (Chile, Germany (2), Greece, Ireland, Spain, Sweden (2), the UK (3), and the USA (3)) were taken into account. Subsequent meta-analysis confirmed HTR3E c.*76G > A (rs56109847 = rs62625044) to be associated with female IBS-D (OR = 1.58; 95% CI (1.18, 2.12)). Complementary expression studies of four GI regions (jejunum, ileum, colon, sigmoid colon) of 66 IBS patients and 42 controls revealed only HTR3E to be robustly expressed. On top, HTR3E transcript levels were significantly reduced in the sigma of IBS patients ( p = 0.0187); more specifically, in those diagnosed with IBS-D ( p = 0.0145). In conclusion, meta-analysis confirmed rs56109847 = rs62625044 as a risk factor for female IBS-D. Expression analysis revealed reduced HTR3E levels in the sigmoid colon of IBS-D patients, which underlines the relevance of HTR3E in the pathogenesis of IBS-D.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Limits to the generalizability of resting-state functional magnetic resonance imaging studies of youth: An examination of ABCD Study® baseline data - Kelly T. Cosgrove; Timothy J. McDermott; Evan J. White; Matthew W. Mosconi; Wesley K. Thompson; Martin P. Paulus; Carlos Cardenas-Iniguez; Robin L. Aupperle (Brain Imaging and Behavior, 2022)

Genetic examination of historical North Atlantic right whale ( Eubalaena glacialis ) bone specimens from the eastern North Atlantic: Insights into species history, transoceanic population structure, and genetic diversity - Brenna A. Frasier; Leah Springate; Timothy R. Frasier; Seth Brewington; Martin Carruthers; Ragnar Edvardsson; Ramona Harrison; Andrew C. Kitchener; Ingrid Mainland; Vicki E. Szabo (Marine Mammal Science, 2022)
Species monitoring and conservation is increasingly challenging under current climate change scenarios. For the North Atlantic right whale ( Eubalaena glacialis ) this challenge is heightened by the added effects of complicated and uncertain past species demography. Right whales once had a much wider distribution across the North Atlantic Ocean, although the degree to which right whales in the western and eastern North Atlantic were genetically isolated remains unknown. We analyzed DNA from 24 4th–20th century (CE) right whale bone specimens that were collected from 10 historical and archaeological sites in Iceland, the Faroe Islands, and Scotland. Following mtDNA species identification, we obtained 15‐locus nuclear microsatellite profiles from a subset of eight specimens and compared these to contemporary data from animals remaining in the western North Atlantic population. While some specimens share mtDNA haplotypes with the contemporary population, several new haplotypes were found. Moderate mtDNA and nuclear differentiation between the two regions was identified (mtDNA: F ST = 0.0423, Φ ST = 0.041; nuclear DNA: F ST = 0.024). Interpretation of the relationships between animals in the two regions is not simple, and this research highlights the difficulty in conducting such assessments in species with complex histories of unknown structure prior to extensive exploitation.

Managing Marine Growth on Historic Maritime Structures: An Assessment of Perceptions and Current Management Practices - Timothy Baxter; Martin Coombes; Heather Viles (Frontiers in Marine Science, 2022)
Maritime built heritage (e.g., historic harbors, breakwaters, etc.) is found widely along the coastlines of Europe. Due to its age and traditional construction, built heritage may represent important and largely unidentified hotspots of biodiversity in marine and coastal environments. At the same time, marine growth (e.g., seaweed, mussels, barnacles, etc.) found on these structures may provide both deteriorative and protective functions. To ensure future research focusing on the two-way interactions between marine growth and built heritage addresses the concerns of those responsible for their management, attitudes towards the colonization and growth of marine wildlife must first be evaluated. Such attitudes will shape how marine growth is managed at these sites, which in turn may influence biodiversity and built heritage conservation and any associated values. This study assesses how the growth of sessile species and other surface-colonizing organisms is currently perceived and managed by those responsible for maintaining maritime built heritage, with a particular focus on historic structures constructed of natural stone. Responses from a semi-quantitative online questionnaire of harbormasters, coastal engineers, environmental officers, and heritage managers from around the UK (n = 132) were analyzed alongside a series of semi-structured interviews (n = 29). Our results demonstrate that attitudes towards marine growth are generally in agreement among practitioners irrespective of their occupation or the historic maritime structures they are responsible for managing. Perceptions of marine growth are mostly positive, but concerns exist regarding its impacts on maintenance regimes, the condition of mortar, and health and safety. As well as highlighting opportunities for a more integrated approach to biodiversity and built heritage conservation, the concerns identified require further research attention to help address potential barriers and conflicts that may arise in practice.

Interferon-alpha or -beta facilitates SARS-CoV-2 pulmonary vascular infection by inducing ACE2 - Timothy Klouda; Yuan Hao; Hyunbum Kim; Jiwon Kim; Judith Olejnik; Adam J. Hume; Sowntharya Ayyappan; Xuechong Hong; Juan Melero-Martin; Yinshan Fang; Qiong Wang; Xiaobo Zhou; et al. (Angiogenesis, 2022)
Severe viral pneumonia caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is characterized by a hyperinflammatory state typified by elevated circulating pro-inflammatory cytokines, frequently leading to potentially lethal vascular complications including thromboembolism, disseminated intracellular coagulopathy and vasculitis. Though endothelial infection and subsequent endothelial damage have been described in patients with fatal COVID-19, the mechanism by which this occurs remains elusive, particularly given that, under naïve conditions, pulmonary endothelial cells demonstrate minimal cell surface expression of the SARS-CoV-2 binding receptor ACE2. Herein we describe SARS-CoV-2 infection of the pulmonary endothelium in postmortem lung samples from individuals who died of COVID-19, demonstrating both heterogeneous ACE2 expression and endothelial damage. In primary endothelial cell cultures, we show that SARS-CoV-2 infection is dependent on the induction of ACE2 protein expression and that this process is facilitated by type 1 interferon-alpha (IFNα) or -beta(β)—two of the main anti-viral cytokines induced in severe SARS-CoV-2 infection—but not significantly by other cytokines (including interleukin 6 and interferon γ/λ). Our findings suggest that the stereotypical anti-viral interferon response may paradoxically facilitate the propagation of COVID-19 from the respiratory epithelium to the vasculature, raising concerns regarding the use of exogenous IFNα/β in the treatment of patients with COVID-19.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Has taxonomic vandalism gone too far? A case study, the rise of the pay-to-publish model and the pitfalls of Morchella systematics - Michael Loizides; Pablo Alvarado; Pierre-Arthur Moreau; Boris Assyov; Viktorie Halasů; Marc Stadler; Andrea Rinaldi; Guilhermina Marques; Georgios I. Zervakis; Jan Borovička; Nicolas Van Vooren; Tine Grebenc; et al. (Mycological Progress, 2022)

Evaluation of pharmacogenomics and hepatic nuclear imaging–related covariates by population pharmacokinetic models of irinotecan and its metabolites - Zheng Liu; Jennifer H. Martin; Winston Liauw; Sue-Anne McLachlan; Emma Link; Anetta Matera; Michael Thompson; Michael Jefford; Rod J. Hicks; Carleen Cullinane; Athena Hatzimihalis; Ian Campbell; et al. (European Journal of Clinical Pharmacology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Soil properties as key predictors of global grassland production: Have we overlooked micronutrients? - Dajana Radujković; Erik Verbruggen; Eric W. Seabloom; Michael Bahn; Lori A. Biederman; Elizabeth T. Borer; Elizabeth H. Boughton; Jane A. Catford; Matteo Campioli; Ian Donohue; Anne Ebeling; Anu Eskelinen; et al. (Ecology Letters, 2021)
Fertilisation experiments have demonstrated that nutrient availability is a key determinant of biomass production and carbon sequestration in grasslands. However, the influence of nutrients in explaining spatial variation in grassland biomass production has rarely been assessed. Using a global dataset comprising 72 sites on six continents, we investigated which of 16 soil factors that shape nutrient availability associate most strongly with variation in grassland aboveground biomass. Climate and N deposition were also considered. Based on theory‐driven structural equation modelling, we found that soil micronutrients (particularly Zn and Fe) were important predictors of biomass and, together with soil physicochemical properties and C:N, they explained more unique variation (32%) than climate and N deposition (24%). However, the association between micronutrients and biomass was absent in grasslands limited by NP. These results highlight soil properties as key predictors of global grassland biomass production and point to serial co‐limitation by NP and micronutrients.

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

Nanopore-based metagenomics analysis reveals prevalence of mobile antibiotic and heavy metal resistome in wastewater - Cristina Martin; Brooke Stebbins; Asha Ajmani; Arianna Comendul; Steve Hamner; Nur A. Hasan; Rita Colwell; Timothy Ford (Ecotoxicology, 2021)

Species loss due to nutrient addition increases with spatial scale in global grasslands - Eric W. Seabloom; Evan Batzer; Jonathan M. Chase; W. Stanley Harpole; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Isabel C. Barrio; Lori Biederman; Elizabeth H. Boughton; Miguel N. Bugalho; Maria C. Caldeira; et al. (Ecology Letters, 2021)
The effects of altered nutrient supplies and herbivore density on species diversity vary with spatial scale, because coexistence mechanisms are scale dependent. This scale dependence may alter the shape of the species–area relationship (SAR), which can be described by changes in species richness ( S ) as a power function of the sample area ( A ): S = cA z , where c and z are constants. We analysed the effects of experimental manipulations of nutrient supply and herbivore density on species richness across a range of scales (0.01–75 m 2 ) at 30 grasslands in 10 countries. We found that nutrient addition reduced the number of species that could co‐occur locally, indicated by the SAR intercepts (log c ), but did not affect the SAR slopes ( z ). As a result, proportional species loss due to nutrient enrichment was largely unchanged across sampling scales, whereas total species loss increased over threefold across our range of sampling scales.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

A hidden Markov model for estimating age‐specific survival when age and size are uncertain - Timothy A. Gowan; Michael D. Tringali; Jeffrey A. Hostetler; Julien Martin; Leslie I. Ward‐Geiger; Jennifer M. Johnson (Ecology, 2021)
Estimates of age‐specific survival probabilities are needed for age‐structured population models and to inform conservation decisions. However, determining the age of individuals in wildlife populations is often problematic. We present a hidden Markov model for estimating age‐specific survival from capture–recapture or capture–recapture–recovery data when age is unknown and indicators of age, such as size and growth layer counts, are imprecise. The model is evaluated through simulations, and its implementation is illustrated with maximum likelihood and Bayesian approaches in commonly used software. The model is then applied to genetic capture–recapture data of Florida manatees to estimate age‐ and time‐variant survival probabilities. The approach is broadly applicable to studies aiming to quantify age‐specific effects of environmental change and management actions on population dynamics, including studies that rely on minimally invasive methods such as genetic and photo identification.

Mutualism disruption by an invasive ant reduces carbon fixation for a foundational East African ant‐plant - Patrick D. Milligan; Timothy A. Martin; Grace P. John; Corinna Riginos; Jacob R. Goheen; Scott M. Carpenter; Todd M. Palmer (Ecology Letters, 2021)
Invasive ants shape assemblages and interactions of native species, but their effect on fundamental ecological processes is poorly understood. In East Africa, Pheidole megacephala ants have invaded monodominant stands of the ant‐tree Acacia drepanolobium , extirpating native ant defenders and rendering trees vulnerable to canopy damage by vertebrate herbivores. We used experiments and observations to quantify direct and interactive effects of invasive ants and large herbivores on A. drepanolobium photosynthesis over a 2‐year period. Trees that had been invaded for ≥ 5 years exhibited 69% lower whole‐tree photosynthesis during key growing seasons, resulting from interaction between invasive ants and vertebrate herbivores that caused leaf‐ and canopy‐level photosynthesis declines. We also surveyed trees shortly before and after invasion, finding that recent invasion induced only minor changes in leaf physiology. Our results from individual trees likely scale up, highlighting the potential of invasive species to alter ecosystem‐level carbon fixation and other biogeochemical cycles.

Scenario Planning: Embracing the Potential for Extreme Events in the Colorado River Basin - Andrea K. Gerlak; Katharine L. Jacobs; Amy L. McCoy; Season Martin; Mariana Rivera-Torres; Anna M. Murveit; Amanda J. Leinberger; Timothy Thomure (Climatic Change, 2021)

Persistent COVID-19-associated neurocognitive symptoms in non-hospitalized patients - Joanna Hellmuth; T. Allen Barnett; Breton M. Asken; J. Daniel Kelly; Leonel Torres; Melanie L. Stephens; Bryan Greenhouse; Jeffrey N. Martin; Felicia C. Chow; Steven G. Deeks; Meredith Greene; Bruce L. Miller; et al. (Journal of NeuroVirology, 2021)
As cases of coronavirus disease 2019 (COVID-19) mount worldwide, attention is needed on potential long-term neurologic impacts for the majority of patients who experience mild to moderate illness managed as outpatients. To date, there has not been discussion of persistent neurocognitive deficits in patients with milder COVID-19. We present two cases of non-hospitalized patients recovering from COVID-19 with persistent neurocognitive symptoms. Commonly used cognitive screens were normal, while more detailed testing revealed working memory and executive functioning deficits. An observational cohort study of individuals recovering from COVID-19 (14 or more days following symptom onset) identified that among the first 100 individuals enrolled, 14 were non-hospitalized patients reporting persistent cognitive issues. These 14 participants had a median age of 39 years (interquartile range: 35–56), and cognitive symptoms were present for at least a median of 98 days (interquartile range: 71–120 following acute COVID-19 symptoms); no participants with follow-up evaluation reported symptom resolution. We discuss potential mechanisms to be explored in future studies, including direct viral effects, indirect consequences of immune activation, and immune dysregulation causing auto-antibody production.

Increasing effects of chronic nutrient enrichment on plant diversity loss and ecosystem productivity over time - Eric W. Seabloom; Peter B. Adler; Juan Alberti; Lori Biederman; Yvonne M. Buckley; Marc W. Cadotte; Scott L. Collins; Laura Dee; Philip A. Fay; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; et al. (Ecology, 2021)
Human activities are enriching many of Earth’s ecosystems with biologically limiting mineral nutrients such as nitrogen (N) and phosphorus (P). In grasslands, this enrichment generally reduces plant diversity and increases productivity. The widely demonstrated positive effect of diversity on productivity suggests a potential negative feedback, whereby nutrient‐induced declines in diversity reduce the initial gains in productivity arising from nutrient enrichment. In addition, plant productivity and diversity can be inhibited by accumulations of dead biomass, which may be altered by nutrient enrichment. Over longer time frames, nutrient addition may increase soil fertility by increasing soil organic matter and nutrient pools. We examined the effects of 5–11 yr of nutrient addition at 47 grasslands in 12 countries. Nutrient enrichment increased aboveground live biomass and reduced plant diversity at nearly all sites, and these effects became stronger over time. We did not find evidence that nutrient‐induced losses of diversity reduced the positive effects of nutrients on biomass; however, nutrient effects on live biomass increased more slowly at sites where litter was also increasing, regardless of plant diversity. This work suggests that short‐term experiments may underestimate the long‐term nutrient enrichment effects on global grassland ecosystems.

Hydrobiogeochemistry of Two Catchments in Brazil Under Forest Recovery in an Environmental Services Payment Program - Ricardo de Oliveira Figueiredo; Matheus Martins Simioli; Talita de Varela Utsuni Camargo Jesus; Patrícia Porta Nova da Cruz; Gustavo Bayma; Sandra Furlan Nogueira; Timothy Richard Green; Plínio Barbosa de Camargo (Environmental Monitoring and Assessment, 2021)

Analysis of CMIP6 atmospheric moisture fluxes and the implications for projections of future change in mean and heavy rainfall - Ian G. Watterson; Richard J. Keane; Martin Dix; Tilo Ziehn; Timothy Andrews; Yongming Tang (International Journal of Climatology, 2021)
Motivated by the wide range of projections of regional rainfall (or precipitation, pr) based on the CMIP5 ensemble of global climate models, we investigate the atmospheric moisture budget of idealized rising‐CO 2 (1pctCO2) simulations from 10 models submitted to CMIP6. We use the new CMIP6 standard variables, the vertically integrated eastward and northward moisture flux, and provide a multi‐model assessment of these, their convergence (conv), along with water vapour path (prw). Seasonal climatologies of a 20‐year base climate for pr, prw, flux, and conv match well those from the ECMWF's Reanalysis 5. In addition, composites ‘H’ of quantities for months in the top decile of monthly rainfall, calculated at each model grid point, produce a field of heavy rainfall, on average double that of the mean. Spatial correlation coefficients ( r ) between the pr and conv fields are typically .7 in each season. This rises to .9 for the corresponding H fields, due to the important link between moisture convergence and heavy rainfall. Fields of standardized change (Δ), or change per degree of global warming, were calculated. The ensemble‐mean Δpr is only weakly correlated with the base climate pr, and likewise for conv. However, the prw change is highly correlated with the base prw, pointing to the importance of the “thermodynamic” change in that variable. Globally, the net Δconv is highly correlated with Δpr, around .9. This rises to .95 for the heavy‐rain composites. Relationships between changes in pr and other components hold at grid points also, when the individual model results are correlated. Clearly, there is a dependence in the change in pr with that in conv, particularly for heavy rainfall. Assessment of a larger ensemble from CMIP6, using the new flux variables, would improve the evaluation of these processes, and potentially allow more confident projections in future rainfall changes.

Breaks of macrosynteny and collinearity among moth bean (Vigna aconitifolia), cowpea (V. unguiculata), and common bean (Phaseolus vulgaris) - Ana Rafaela da S. Oliveira; Lívia do Vale Martins; Fernanda de O. Bustamante; María Muñoz-Amatriaín; Timothy Close; Antônio F. da Costa; Ana Maria Benko-Iseppon; Andrea Pedrosa-Harand; Ana Christina Brasileiro-Vidal (Chromosome Research, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

How many, how far? Quantitative models of Neolithic land use for six wetland sites on the northern Alpine forelands between 4300 and 3700 bc - Tilman Baum; Martin Mainberger; Timothy Taylor; Willy Tinner; Albert Hafner; Renate Ebersbach (Vegetation History and Archaeobotany, 2020)

Seminal fluid protein divergence among populations exhibiting postmating prezygotic reproductive isolation - Martin D. Garlovsky; Caroline Evans; Mathew A. Rosenow; Timothy L. Karr; Rhonda R. Snook (Molecular Ecology, 2020)
Despite holding a central role in fertilization, reproductive traits often show elevated rates of evolution and diversification. The rapid evolution of seminal fluid proteins (Sfps) within populations is predicted to cause mis‐signalling between the male ejaculate and the female during and after mating resulting in postmating prezygotic (PMPZ) isolation between populations. Crosses between Drosophila montana populations show PMPZ isolation in the form of reduced fertilization success in both noncompetitive and competitive contexts. Here we test whether male ejaculate proteins produced in the accessory glands or ejaculatory bulb differ between populations using liquid chromatography tandem mass spectrometry. We find more than 150 differentially abundant proteins between populations that may contribute to PMPZ isolation, including a number of proteases, peptidases and several orthologues of Drosophila melanogaster Sfps known to mediate fertilization success. Males from the population that elicit the stronger PMPZ isolation after mating with foreign females typically produced greater quantities of Sfps. The accessory glands and ejaculatory bulb show enrichment for different gene ontology (GO) terms and the ejaculatory bulb contributes more differentially abundant proteins. Proteins with a predicted secretory signal evolve faster than nonsecretory proteins. Finally, we take advantage of quantitative proteomics data for three Drosophila species to determine shared and unique GO enrichments of Sfps between taxa and which potentially mediate PMPZ isolation. Our study provides the first high‐throughput quantitative proteomic evidence showing divergence of reproductive proteins between populations that exhibit PMPZ isolation.

Microbial tropicalization driven by a strengthening western ocean boundary current - Lauren F. Messer; Martin Ostrowski; Martina A. Doblin; Katherina Petrou; Mark E. Baird; Timothy Ingleton; Andrew Bissett; Jodie Van de Kamp; Tiffanie Nelson; Ian Paulsen; Levente Bodrossy; Jed A. Fuhrman; et al. (Global Change Biology, 2020)
Western boundary currents (WBCs) redistribute heat and oligotrophic seawater from the tropics to temperate latitudes, with several displaying substantial climate change‐driven intensification over the last century. Strengthening WBCs have been implicated in the poleward range expansion of marine macroflora and fauna, however, the impacts on the structure and function of temperate microbial communities are largely unknown. Here we show that the major subtropical WBC of the South Pacific Ocean, the East Australian Current (EAC), transports microbial assemblages that maintain tropical and oligotrophic ( k ‐strategist) signatures, to seasonally displace more copiotrophic ( r ‐strategist) temperate microbial populations within temperate latitudes of the Tasman Sea. We identified specific characteristics of EAC microbial assemblages compared with non‐EAC assemblages, including strain transitions within the SAR11 clade, enrichment of Prochlorococcus , predicted smaller genome sizes and shifts in the importance of several functional genes, including those associated with cyanobacterial photosynthesis, secondary metabolism and fatty acid and lipid transport. At a temperate time‐series site in the Tasman Sea, we observed significant reductions in standing stocks of total carbon and chlorophyll a , and a shift towards smaller phytoplankton and carnivorous copepods, associated with the seasonal impact of the EAC microbial assemblage. In light of the substantial shifts in microbial assemblage structure and function associated with the EAC, we conclude that climate‐driven expansions of WBCs will expand the range of tropical oligotrophic microbes, and potentially profoundly impact the trophic status of temperate waters.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Assessing functions of movement in a Great Plains endemic fish - David S. Ruppel; V. Alex Sotola; Cody A. Craig; Noland H. Martin; Timothy H. Bonner (Environmental Biology of Fishes, 2020)

A catastrophic tropical drought kills hydraulically vulnerable tree species - Jennifer S. Powers; German Vargas G.; Timothy J. Brodribb; Naomi B. Schwartz; Daniel Pérez‐Aviles; Chris M. Smith‐Martin; Justin M. Becknell; Filippo Aureli; Roger Blanco; Erick Calderón‐Morales; Julio C. Calvo‐Alvarado; Ana Julieta Calvo‐Obando; et al. (Global Change Biology, 2020)
Drought‐related tree mortality is now a widespread phenomenon predicted to increase in magnitude with climate change. However, the patterns of which species and trees are most vulnerable to drought, and the underlying mechanisms have remained elusive, in part due to the lack of relevant data and difficulty of predicting the location of catastrophic drought years in advance. We used long‐term demographic records and extensive databases of functional traits and distribution patterns to understand the responses of 20–53 species to an extreme drought in a seasonally dry tropical forest in Costa Rica, which occurred during the 2015 El Niño Southern Oscillation event. Overall, species‐specific mortality rates during the drought ranged from 0% to 34%, and varied little as a function of tree size. By contrast, hydraulic safety margins correlated well with probability of mortality among species, while morphological or leaf economics spectrum traits did not. This firmly suggests hydraulic traits as targets for future research.

Evaluation of Different Quality-Relevant Aspects of Closed System Transfer Devices (CSTDs) - Ahmed Besheer; Hanns-Christian Mahler; Anja Matter-Schwald; Sergio Mompart Barrenechea; Martin Vogt; Pascal Chalus; Pauline Heymes; Timothy Pillow; Andrea Kirste; Patrick Favrod; Susanne Joerg; Roman Mathaes (Pharmaceutical Research, 2020)

Correction to: Bilingualism Is Associated with a Delayed Onset of Dementia but Not with a Lower Risk of Developing it: a Systematic Review with Meta-Analyses - Stefano Brini; Hamid R. Sohrabi; Jeffrey J. Hebert; Mitchell R. L. Forrest; Matti Laine; Heikki Hämäläinen; Mira Karrasch; Jeremiah J. Peiffer; Ralph N. Martins; Timothy J. Fairchild (Neuropsychology Review, 2020)
The original version of this article unfortunately contained the following mistakes.

Bilingualism Is Associated with a Delayed Onset of Dementia but Not with a Lower Risk of Developing it: a Systematic Review with Meta-Analyses - Stefano Brini; Hamid R. Sohrabi; Jeffrey J. Hebert; Mitchell R. L. Forrest; Matti Laine; Heikki Hämäläinen; Mira Karrasch; Jeremiah J. Peiffer; Ralph N. Martins; Timothy J. Fairchild (Neuropsychology Review, 2020)
Some studies have linked bilingualism with a later onset of dementia, Alzheimer’s disease (AD), and mild cognitive impairment (MCI). Not all studies have observed such relationships, however. Differences in study outcomes may be due to methodological limitations and the presence of confounding factors within studies such as immigration status and level of education. We conducted the first systematic review with meta-analysis combining cross-sectional studies to explore if bilingualism might delay symptom onset and diagnosis of dementia, AD, and MCI. Primary outcomes included the age of symptom onset, the age at diagnosis of MCI or dementia, and the risk of developing MCI or dementia. A secondary outcome included the degree of disease severity at dementia diagnosis. There was no difference in the age of MCI diagnosis between monolinguals and bilinguals [mean difference: 3.2; 95% confidence intervals (CI): −3.4, 9.7]. Bilinguals vs. monolinguals reported experiencing AD symptoms 4.7 years (95% CI: 3.3, 6.1) later. Bilinguals vs. monolinguals were diagnosed with dementia 3.3 years (95% CI: 1.7, 4.9) later. Here, 95% prediction intervals showed a large dispersion of effect sizes (−1.9 to 8.5). We investigated this dispersion with a subgroup meta-analysis comparing studies that had recruited participants with dementia to studies that had recruited participants with AD on the age of dementia and AD diagnosis between mono- and bilinguals. Results showed that bilinguals vs. monolinguals were 1.9 years (95% CI: −0.9, 4.7) and 4.2 (95% CI: 2.0, 6.4) older than monolinguals at the time of dementia and AD diagnosis, respectively. The mean difference between the two subgroups was not significant. There was no significant risk reduction (odds ratio: 0.89; 95% CI: 0.68–1.16) in developing dementia among bilinguals vs. monolinguals. Also, there was no significant difference (Hedges’ g = 0.05; 95% CI: −0.13, 0.24) in disease severity at dementia diagnosis between bilinguals and monolinguals, despite bilinguals being significantly older. The majority of studies had adjusted for level of education suggesting that education might not have played a role in the observed delay in dementia among bilinguals vs. monolinguals. Although findings indicated that bilingualism was on average related to a delayed onset of dementia, the magnitude of this relationship varied across different settings. This variation may be due to unexplained heterogeneity and different sources of bias in the included studies. Registration: PROSPERO CRD42015019100.

Scale dependency of conservation outcomes in a forest‐offsetting scheme - Marta Lisli Giannichi; Yoni Gavish; Timothy R. Baker; Martin Dallimer; Guy Ziv (Conservation Biology, 2020)
Offset schemes help avoid or revert habitat loss through protection of existing habitat (avoided deforestation), through the restoration of degraded areas (natural regrowth), or both. The spatial scale of an offset scheme may influence which of these 2 outcomes is favored and is an important aspect of the scheme's design. However, how spatial scale influences the trade‐offs between the preservation of existing habitat and restoration of degraded areas is poorly understood. We used the largest forest offset scheme in the world, which is part of the Brazilian Forest Code, to explore how implementation at different spatial scales may affect the outcome in terms of the area of avoided deforestation and area of regrowth. We employed a numerical simulation of trade between buyers (i.e., those who need to offset past deforestation) and sellers (i.e., landowners with exceeding native vegetation) in the Brazilian Amazon to estimate potential avoided deforestation and regrowth at different spatial scales of implementation. Allowing offsets over large spatial scales led to an area of avoided deforestation 12 times greater than regrowth, whereas restricting offsets to small spatial scales led to an area of regrowth twice as large as avoided deforestation. The greatest total area (avoided deforestation and regrowth combined) was conserved when the spatial scale of the scheme was small, especially in locations that were highly deforested. To maximize conservation gains from avoided deforestation and regrowth, the design of the Brazilian forest‐offset scheme should focus on restricting the spatial scale in which offsets occur. Such a strategy could help ensure conservation benefits are localized and promote the recovery of degraded areas in the most threatened forest landscapes.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Effect of different doses of supervised aerobic exercise on heart rate recovery in inactive adults who are overweight or obese: results from E-MECHANIC - Christoph Höchsmann; James L. Dorling; John W. Apolzan; Neil M. Johannsen; Daniel S. Hsia; Timothy S. Church; Corby K. Martin (European Journal of Applied Physiology, 2019)

Presence and genetic variability of Piscine orthoreovirus genotype 1 (PRV‐1) in wild salmonids in Northern Europe and North Atlantic Ocean - Niccoló Vendramin; Argelia Cuenca; Juliane Sørensen; Anna L. F. Alencar; Debes H. Christiansen; Jan A. Jacobsen; Charlotte Axen; François Lieffrig; Neil M. Ruane; Patrick Martin; Timothy Sheehan; Tine M. Iburg; et al. (Journal of Fish Diseases, 2019)
Piscine orthoreovirus genotype 1 (PRV‐1) is widespread in farmed Atlantic salmon ( Salmo salar L.) populations in northern Europe, Canada and Chile. PRV‐1 occurs in wild fish in Norway and Canada; however, little information of its geographical distribution in wild populations is currently available, and the effect of PRV‐1 infection in wild populations is currently unknown. In this study, we present the findings of a survey conducted on 1,130 wild salmonids sampled in Denmark, Sweden, Ireland, Faroe Islands, France, Belgium and Greenland between 2008 and 2017. PRV‐1 is reported for the first time in wild salmonids in Denmark, Sweden, Faroe Island and Ireland. The annual PRV‐1 prevalence ranged from 0% in France, Belgium and Greenland to 43% in Faroe Islands. In total, 66 samples tested positive for PRV‐1, including Atlantic salmon broodfish returning to spawn and Atlantic salmon collected at the feeding ground north of Faroe Islands. The phylogenetic analysis of S1 sequences of the PRV‐1 isolates obtained in this survey did not show systematic geographical distribution. This study sheds light on the spread and genetic diversity of the virus identified in populations of free‐living fish and provides rationale for screening wild broodfish used in restocking programmes.

Plant richness and composition in hardwood forest understories vary along an acidic deposition and soil-chemical gradient in the northeastern United States - Michael R. Zarfos; Martin Dovciak; Gregory B. Lawrence; Todd C. McDonnell; Timothy J. Sullivan (Plant and Soil, 2019)

IVIG Delays Onset in a Mouse Model of Gerstmann-Sträussler-Scheinker Disease - Huiying Gu; Yvonne Kirchhein; Timothy Zhu; Gang Zhao; Hongjun Peng; Eileen Du; Junyi Liu; James A. Mastrianni; Martin R. Farlow; Richard Dodel; Yansheng Du (Molecular Neurobiology, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Definition of a temporal distribution index for high temporal resolution precipitation data over Peninsular Spain and the Balearic Islands: the fractal dimension; and its synoptic implications - Oliver Meseguer-Ruiz; Timothy J. Osborn; Pablo Sarricolea; Philip D. Jones; Jorge Olcina Cantos; Roberto Serrano-Notivoli; Javier Martin-Vide (Climate Dynamics, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Assessing the interplay between canopy energy balance and photosynthesis with cellulose δ18O: large-scale patterns and independent ground-truthing - Brent R. Helliker; Xin Song; Michael L. Goulden; Kenneth Clark; Paul Bolstad; J. William Munger; Jiquan Chen; Asko Noormets; David Hollinger; Steve Wofsy; Timothy Martin; Dennis Baldocchi; et al. (Oecologia, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

A Resilience Framework for Chronic Exposures: Water Quality and Ecosystem Services in Coastal Social-Ecological Systems - Nathaniel H. Merrill; Kate K. Mulvaney; David M. Martin; Marnita M. Chintala; Walter Berry; Timothy R. Gleason; Stephen Balogh; Austin T. Humphries (Coastal Management, 2018)

Inter- and intra-species intercropping of barley cultivars and legume species, as affected by soil phosphorus availability - Tegan Darch; Courtney D. Giles; Martin S. A. Blackwell; Timothy S. George; Lawrie K. Brown; Daniel Menezes-Blackburn; Charles A. Shand; Marc I. Stutter; David G. Lumsdon; Malika M. Mezeli; Renate Wendler; Hao Zhang; et al. (Plant and Soil, 2018)

Opportunities for mobilizing recalcitrant phosphorus from agricultural soils: a review - Daniel Menezes-Blackburn; Courtney Giles; Tegan Darch; Timothy S. George; Martin Blackwell; Marc Stutter; Charles Shand; David Lumsdon; Patricia Cooper; Renate Wendler; Lawrie Brown; Danilo S. Almeida; et al. (Plant and Soil, 2018)

Soil Base Saturation Combines with Beech Bark Disease to Influence Composition and Structure of Sugar Maple-Beech Forests in an Acid Rain-Impacted Region - Gregory B. Lawrence; Todd C. McDonnell; Timothy J. Sullivan; Martin Dovciak; Scott W. Bailey; Michael R. Antidormi; Michael R. Zarfos (Ecosystems, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

Rare long‐distance dispersal of a marine angiosperm across the Pacific Ocean - Timothy M. Smith; Paul H. York; Bernardo R. Broitman; Martin Thiel; Graeme C. Hays; Erik van Sebille; Nathan F. Putman; Peter I. Macreadie; Craig D. H. Sherman (Global Ecology and Biogeography, 2018)
Aim Long‐distance dispersal (LDD) events occur rarely but play a fundamental role in shaping species biogeography. Lying at the heart of island biogeography theory, LDD relies on unusual events to facilitate colonization of new habitats and range expansion. Despite the importance of LDD, it is inherently difficult to quantify due to the rarity of such events. We estimate the probability of LDD of the seagrass Heterozostera nigricaulis , a common Australian species, across the Pacific Ocean to colonize South America. Location Coastal Chile, Australia and the Pacific Ocean. Methods Genetic analyses of H. nigricaulis collected from Chile and Australia were used to assess the relationship between the populations and levels of clonality. Ocean surface current models were used to predict the probability of propagules dispersing from south‐east Australia to central Chile and shipping data used to determine the likelihood of anthropogenic dispersal. Results Our study infers that the seagrass H. nigricaulis dispersed from Australia across the entire width of the Pacific ( c. 14,000 km) to colonize South America on two occasions. Genetic analyses reveal that these events led to two large isolated clones, one of which covers a combined area of 3.47 km 2 . Oceanographic models estimate the arrival probability of a dispersal propagule within 3 years to be at most 0.00264%. Early shipping provides a potential alternative dispersal vector, yet few ships sailed from SE Australia to Chile prior to the first recording of H. nigricaulis and the lack of more recent and ongoing introductions demonstrate the rarity of such dispersal. Main conclusions These findings demonstrate LDD does occur over extreme distances despite very low probabilities. The large number of propagules (100s of millions) produced over 100s of years suggests that the arrival of propagules in Chile was inevitable and confirms the importance of LDD for species distributions and community ecology.

Screening the ToxCast phase II libraries for alterations in network function using cortical neurons grown on multi-well microelectrode array (mwMEA) plates - Jenna D. Strickland; Matthew T. Martin; Ann M. Richard; Keith A. Houck; Timothy J. Shafer (Archives of Toxicology, 2018)

Charting the Environmental Dimensions of Additive Manufacturing and 3D Printing - Martin Baumers; Joost R. Duflou; William Flanagan; Timothy G. Gutowski; Karel Kellens; Reid Lifset (Journal of Industrial Ecology, 2017)

Environmental Dimensions of Additive Manufacturing: Mapping Application Domains and Their Environmental Implications - Karel Kellens; Martin Baumers; Timothy G. Gutowski; William Flanagan; Reid Lifset; Joost R. Duflou (Journal of Industrial Ecology, 2017)
Summary Additive manufacturing (AM) proposes a novel paradigm for engineering design and manufacturing, which has profound economic, environmental, and security implications. The design freedom offered by this category of manufacturing processes and its ability to locally print almost each designable object will have important repercussions across society. While AM applications are progressing from rapid prototyping to the production of end‐use products, the environmental dimensions and related impacts of these evolving manufacturing processes have yet to be extensively examined. Only limited quantitative data are available on how AM manufactured products compare to conventionally manufactured ones in terms of energy and material consumption, transportation costs, pollution and waste, health and safety issues, as well as other environmental impacts over their full lifetime. Reported research indicates that the specific energy of current AM systems is 1 to 2 orders of magnitude higher compared to that of conventional manufacturing processes. However, only part of the AM process taxonomy is yet documented in terms of its environmental performance, and most life cycle inventory (LCI) efforts mainly focus on energy consumption. From an environmental perspective, AM manufactured parts can be beneficial for very small batches, or in cases where AM‐based redesigns offer substantial functional advantages during the product use phase (e.g., lightweight part designs and part remanufacturing). Important pending research questions include the LCI of AM feedstock production, supply‐chain consequences, and health and safety issues relating to AM.

Pinus taeda forest growth predictions in the 21st century vary with site mean annual temperature and site quality - Carlos A. Gonzalez‐Benecke; Robert O. Teskey; Heather Dinon‐Aldridge; Timothy A. Martin (Global Change Biology, 2017)
Climate projections from 20 downscaled global climate models ( GCM s) were used with the 3‐ PG model to predict the future productivity and water use of planted loblolly pine ( Pinus taeda ) growing across the southeastern United States. Predictions were made using Representative Concentration Pathways ( RCP ) 4.5 and 8.5. These represent scenarios in which total radiative forcing stabilizes before 2100 ( RCP 4.5) or continues increasing throughout the century ( RCP 8.5). Thirty‐six sites evenly distributed across the native range of the species were used in the analysis. These sites represent a range in current mean annual temperature (14.9–21.6°C) and precipitation (1,120–1,680 mm/year). The site index of each site, which is a measure of growth potential, was varied to represent different levels of management. The 3‐ PG model predicted that aboveground biomass growth and net primary productivity will increase by 10%–40% in many parts of the region in the future. At cooler sites, the relative growth increase was greater than at warmer sites. By running the model with the baseline [ CO 2 ] or the anticipated elevated [ CO 2 ], the effect of CO 2 on growth was separated from that of other climate factors. The growth increase at warmer sites was due almost entirely to elevated [ CO 2 ]. The growth increase at cooler sites was due to a combination of elevated [ CO 2 ] and increased air temperature. Low site index stands had a greater relative increase in growth under the climate change scenarios than those with a high site index. Water use increased in proportion to increases in leaf area and productivity but precipitation was still adequate, based on the downscaled GCM climate projections. We conclude that an increase in productivity can be expected for a large majority of the planted loblolly pine stands in the southeastern United States during this century.

Psychosocial morbidity in TP53 mutation carriers: is whole-body cancer screening beneficial? - Kate A. McBride; Mandy L. Ballinger; Timothy E. Schlub; Mary-Anne Young; Martin H. N. Tattersall; Judy Kirk; Ros Eeles; Emma Killick; Leslie G. Walker; Sue Shanley; David M. Thomas; Gillian Mitchell (Familial Cancer, 2017)

Important Plant Areas: revised selection criteria for a global approach to plant conservation - Iain Darbyshire; Seona Anderson; Anna Asatryan; Andrew Byfield; Martin Cheek; Colin Clubbe; Zeineb Ghrabi; Timothy Harris; Charlie D. Heatubun; James Kalema; Sékou Magassouba; Ben McCarthy; et al. (Biodiversity and Conservation, 2017)

Navigating the ‘broad freeway’: ocean currents and inland isolation drive diversification in the Pandanus tectorius complex (Pandanaceae) - Timothy Gallaher; Martin W. Callmander; Sven Buerki; Suzuki Setsuko; Sterling C. Keeley (Journal of Biogeography, 2017)
Aim To test for and describe the genetic structure of the Pandanus tectorius complex, a group of closely related ocean‐dispersed plants and members of the Indo‐Pacific coastal strand community. Location Tropical Indo‐Pacific (coastal East Africa to Polynesia). Methods We sampled 535 individuals (46 localities) from throughout the range of the complex. Fifteen microsatellite loci were used to detect and characterize population structure and estimate migration rates between island groups and broad regions. Results Hierarchical population structure was detected. Samples group into an eastern cluster (Hawaii and coastal South‐Central Pacific localities) and a western cluster [Western Pacific (WP) through Indian Ocean]. Within these two clusters, at least six regional subclusters were detected including samples from the Indian Ocean + South China Sea (SCS), Ogasawara Islands, WP, inland South‐Central Pacific, coastal South‐Central Pacific and Hawaii. Migration rates between regions are low leading to isolation and genetic differentiation while within regions, rates are much higher. In most cases, inland populations are genetically differentiated from nearby coastal counterparts. Main conclusions Substantial population structure occurs across the range of the P. tectorius complex due to dispersal limitation across stretches of open ocean and patterns of ocean currents. Low levels of asymmetric westward migration, consistent with the direction of ocean currents in the Pacific, links Hawaii and the South‐Central Pacific with populations further to the west preventing complete isolation. SCS + Indian Ocean populations are distinct from those in the Pacific due to limited dispersal between these regions. The isolation of inland populations on several islands also contributes to genetic differentiation. While population clusters have a clear geographical basis they are not completely congruent with previously recognized taxa.

Genetic control of growth and shoot phenology in juvenile loblolly pine (Pinus taeda L.) clonal trials - Tania Quesada; Liliana M. Parisi; Dudley A. Huber; Salvador A. Gezan; Timothy A. Martin; John M. Davis; Gary F. Peter (Tree Genetics & Genomes, 2017)

Social context has differential effects on acquisition of nicotine self-administration in male and female rats - Natalie A. Peartree; Kayla N. Hatch; Julianna G. Goenaga; Nora R. Dado; Hanna Molla; Martin A. Dufwenberg; Allegra Campagna; Rachel Mendoza; Timothy H.C. Cheung; Joshua S. Talboom; Janet L. Neisewander (Psychopharmacology, 2017)

Does the combination of citrate and phytase exudation in Nicotiana tabacum promote the acquisition of endogenous soil organic phosphorus? - Courtney D. Giles; Timothy S. George; Lawrie K. Brown; Malika M. Mezeli; Alan E. Richardson; Charles A. Shand; Renate Wendler; Tegan Darch; Daniel Menezes-Blackburn; Patricia Cooper; Marc I. Stutter; David G. Lumsdon; et al. (Plant and Soil, 2017)

Evaluation of the efficacy, acceptability and palatability of calcium montmorillonite clay used to reduce aflatoxin B1 dietary exposure in a crossover study in Kenya - Abigael O. Awuor; Ellen Yard; Johnni H. Daniel; Collen Martin; Christine Bii; Amelia Romoser; Elvis Oyugi; Sarah Elmore; Samwel Amwayi; John Vulule; Nicholas C. Zitomer; Michael E. Rybak; et al. (Food Additives & Contaminants: Part A, 2017)

Vibrotactile cuing revisited to reveal a possible challenge to sensorimotor adaptation - Beom-Chan Lee; Timothy A. Thrasher; Charles S. Layne; Bernard J. Martin (Experimental Brain Research, 2016)

Mapping marine debris across coastal communities in Belize: developing a baseline for understanding the distribution of litter on beaches using geographic information systems - Paulita Bennett-Martin; Christy C. Visaggi; Timothy L. Hawthorne (Environmental Monitoring and Assessment, 2016)

Integration of new processes and geothermal heat into a wood processing cluster - Martin J. Atkins; Michael R. W. Walmsley; Timothy G. Walmsley (Clean Technologies and Environmental Policy, 2016)

Functional, Phylogenetic and Host-Geographic Signatures of Labyrinthula spp. Provide for Putative Species Delimitation and a Global-Scale View of Seagrass Wasting Disease - Daniel L. Martin; Ylenia Chiari; Emily Boone; Timothy D. Sherman; Cliff Ross; Sandy Wyllie-Echeverria; Joseph K. Gaydos; Anne A. Boettcher (Estuaries and Coasts, 2016)

Do the rich get richer? Varying effects of tree species identity and diversity on the richness of understory taxa - Juliette Chamagne; C. E. Timothy Paine; Donald R. Schoolmaster; Robert Stejskal; Daniel Volarřík; Jan Šebesta; Filip Trnka; Tomáš Koutecký; Petr Švarc; Martin Svátek; Andy Hector; Radim Matula (Ecology, 2016)
Understory herbs and soil invertebrates play key roles in soil formation and nutrient cycling in forests. Studies suggest that diversity in the canopy and in the understory are positively associated, but these studies often confound the effects of tree species diversity with those of tree species identity and abiotic conditions. We combined extensive field sampling with structural equation modeling to evaluate the simultaneous effects of tree diversity on the species diversity of understory herbs, beetles, and earthworms. The diversity of earthworms and saproxylic beetles was directly and positively associated with tree diversity, presumably because species of both these taxa specialize on certain species of trees. Tree identity also strongly affected diversity in the understory, especially for herbs, likely as a result of interspecific differences in canopy light transmittance or litter decomposition rates. Our results suggest that changes in forest management will disproportionately affect certain understory taxa. For instance, changes in canopy diversity will affect the diversity of earthworms and saproxylic beetles more than changes in tree species composition, whereas the converse would be expected for understory herbs and detritivorous beetles. We conclude that the effects of tree diversity on understory taxa can vary from positive to negative and may affect biogeochemical cycling in temperate forests. Thus, maintaining high diversity in temperate forests can promote the diversity of multiple taxa in the understory.

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Integrated environmental assessment to explore water resources management in Al Jabal Al Akhdar, Sultanate of Oman - Mohammed Saif Al-Kalbani; Martin Francis Price; Timothy O’Higgins; Mushtaque Ahmed; Asma Abahussain (Regional Environmental Change, 2016)

Rock geochemistry induces stress and starvation responses in the bacterial proteome - Casey C. Bryce; Thierry Le Bihan; Sarah F. Martin; Jesse P. Harrison; Timothy Bush; Bryan Spears; Alanna Moore; Natalie Leys; Bo Byloos; Charles S. Cockell (Environmental Microbiology, 2016)
Summary Interactions between microorganisms and rocks play an important role in Earth system processes. However, little is known about the molecular capabilities microorganisms require to live in rocky environments. Using a quantitative label‐free proteomics approach, we show that a model bacterium ( C upriavidus metallidurans CH 34) can use volcanic rock to satisfy some elemental requirements, resulting in increased rates of cell division in both magnesium‐ and iron‐limited media. However, the rocks also introduced multiple new stresses via chemical changes associated with pH , elemental leaching and surface adsorption of nutrients that were reflected in the proteome. For example, the loss of bioavailable phosphorus was observed and resulted in the upregulation of diverse phosphate limitation proteins, which facilitate increase phosphate uptake and scavenging within the cell. Our results revealed that despite the provision of essential elements, rock chemistry drives complex metabolic reorganization within rock‐dwelling organisms, requiring tight regulation of cellular processes at the protein level. This study advances our ability to identify key microbial responses that enable life to persist in rock environments.

Fighting hospital infection with new antibiotic molecules derived from microalgae: the NoMorFilm EU project - Amaral Raquel; Martins Clara; Assunção Mariana; Santos Lília; Soto Sara; Lombó Felipe; Römling Ute; Tredici Mario; Ortiz Fernando; Jensen Henrik; Foster Timothy; Rodolfi Liliana; et al. (Frontiers in Marine Science, 2016)

Reconciling the role of organic matter pathways in aquatic food webs by measuring multiple tracers in individuals - Timothy D. Jardine; Ryan Woods; Jonathan Marshall; James Fawcett; Jaye Lobegeiger; Dominic Valdez; Martin J. Kainz (Ecology, 2015)
Few studies measure multiple ecological tracers in individual organisms, thus limiting our ability to differentiate among organic matter source pathways and understand consequences of dietary variation and the use of external subsidies in complex food webs. We combined two tracers, stable isotope (SI) ratios and fatty acids (FA), to investigate linkages among ecological compartments (water column, benthos, riparian zone) in food webs in waterholes of a dryland river network, the Border Rivers in southwestern Queensland, Australia. Comprehensive analyses of sources (plankton, periphyton, leaf litter, riparian grasses) and animals (benthic insects, mollusks, large crustaceans, fishes) for SI and FA showed that all three zones contribute to animal biomass, depending on species and life stage. Large fishes derived a subsidy from the riparian/floodplain zone, likely through the consumption of terrestrial and semi‐aquatic insects and prawns that fed on detritivorous insects. Importantly, post‐larval bony bream ( Nematalosa erebi ) and golden perch ( Macquaria ambigua ) were tightly connected to the water column, as evidenced by 13 C‐depleted, 15 N‐enriched isotope ratios and a high content of plankton‐derived polyunsaturated fatty acids (eicosapentaenoic acid [EPA; 20:5ω3] and docosahexaenoic acid [DHA; 22:6ω3]). These observations were consistent with expectations from nutritional requirements of fish early life stages and habitat changes associated with maturity. These results highlight the importance of high‐quality foods during early development of fishes, and show that attempting to attribute food‐web production to a single source pathway overlooks important but often subtle subsidies that maintain viable populations. A complete understanding of food‐web dynamics must consider both quantity and quality of different available organic matter sources. This understanding can be achieved with a combined SI and FA approach, but more controlled dietary studies are needed to estimate how FA profiles are modified by animals when consuming a diverse range of diets of variable quality.

Effects of local meteorology and aerosols on ozone and nitrogen dioxide retrievals from OMI and pandora spectrometers in Maryland, USA during DISCOVER-AQ 2011 - Andra J. Reed; Anne M. Thompson; Debra E. Kollonige; Douglas K. Martins; Maria A. Tzortziou; Jay R. Herman; Timothy A. Berkoff; Nader K. Abuhassan; Alexander Cede (Journal of Atmospheric Chemistry, 2015)

Genetics of skin color variation in Europeans: genome-wide association studies with functional follow-up - Fan Liu; Mijke Visser; David L. Duffy; Pirro G. Hysi; Leonie C. Jacobs; Oscar Lao; Kaiyin Zhong; Susan Walsh; Lakshmi Chaitanya; Andreas Wollstein; Gu Zhu; Grant W. Montgomery; et al. (Human Genetics, 2015)

Environmental conditions and physiological state influence estuarine movements of homing sockeye salmon - S. Matthew Drenner; Scott G. Hinch; Eduardo G. Martins; Nathan B. Furey; Timothy D. Clark; Steven J. Cooke; David A. Patterson; David Robichaud; David W. Welch; Anthony P. Farrell; Richard E. Thomson (Fisheries Oceanography, 2015)
The reproductive migration of anadromous salmonids through estuarine waters is one of the most challenging stages of their life cycle, yet little is known about the environmental and physiological conditions that influence migratory behaviour. We captured, sampled tissues, tagged and released 365 sockeye salmon ( Oncorhynchus nerka ) homing through inner coastal waters towards the Fraser River, British Columbia, Canada. Biotelemetry was used to assess the behaviour of individual sockeye salmon approaching estuarine waters and at river entry, which were related to both fish physiological condition at release and to prevailing environmental conditions. Sockeye salmon tended to stay close to the shore, migrated during the day, and movements were related to tide. Sockeye salmon migration rate was linked to wind‐induced currents, salinity and an individual's physiological state, but these factors were specific to location and stock. We propose that wind‐induced currents exposed sockeye salmon entering the estuary to stronger olfactory cues associated with Fraser River water, which in turn resulted in faster migration rates presumably due to either an increased ability for olfactory navigation and/or advanced reproductive schedule through a neuroendocrine response to olfactory cues. However, once the migration had progressed further into more concentrated freshwater of the river plume, sockeye salmon presumably used wind‐induced currents to aid in movements towards the river, which may be associated with energy conservation. Results from this study improve our biological understanding of the movements of Fraser River sockeye salmon and are also broadly relevant to other anadromous salmonids homing in marine environments.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Prevalence and characterisation of non-cholerae Vibrio spp. in final effluents of wastewater treatment facilities in two districts of the Eastern Cape Province of South Africa: implications for public health - Anthony I. Okoh; Timothy Sibanda; Vuyokazi Nongogo; Martins Adefisoye; Osuolale O. Olayemi; Nolonwabo Nontongana (Environmental Science and Pollution Research, 2015)

Whole-genome analyses of DS-1-like human G2P[4] and G8P[4] rotavirus strains from Eastern, Western and Southern Africa - Martin M. Nyaga; Karla M. Stucker; Mathew D. Esona; Khuzwayo C. Jere; Bakari Mwinyi; Annie Shonhai; Enyonam Tsolenyanu; Augustine Mulindwa; Julia N. Chibumbya; Hokororo Adolfine; Rebecca A. Halpin; Sunando Roy; et al. (Virus Genes, 2014)

Evidence of endoplasmic reticulum stress and liver inflammation in the American mink Neovison vison with benign hepatic steatosis - Kirsti Rouvinen-Watt; Catherine Pal; Timothy Martin; Lora Harris; Tessema Astatkie; Darya Kryzskaya; Vesa Kärjä; Anne-Mari Mustonen; Raija Tammi; Markku Tammi; Petteri Nieminen (Journal of Comparative Physiology B, 2014)

Breeding for value in a changing world: past achievements and future prospects - Tim White; John Davis; Salvador Gezan; Jiri Hulcr; Eric Jokela; Matias Kirst; Timothy A. Martin; Gary Peter; Greg Powell; Jason Smith (New Forests, 2014)

On the origin and evolution of apomixis in Boechera - John T. Lovell; Olawale M. Aliyu; Martin Mau; M. Eric Schranz; Marcus Koch; Christiane Kiefer; Bao-Hua Song; Thomas Mitchell-Olds; Timothy F. Sharbel (Plant Reproduction, 2013)

Weed growth and crop performance following hairy vetch, rye, and wheat cover crops in a cool semiarid region - Patrick M. Carr; Richard D. Horsley; Jeffrey J. Gunderson; Timothy J. Winch; Glenn B. Martin (Organic Agriculture, 2013)

In vitro exploration of potential mechanisms of toxicity of the human hepatotoxic drug fenclozic acid - Alison V. M. Rodrigues; Helen E. Rollison; Scott Martin; Sunil Sarda; Timothy Schulz-Utermoehl; Simone Stahl; Frida Gustafsson; Julie Eakins; J. Gerry Kenna; Ian D. Wilson (Archives of Toxicology, 2013)

Volume-based pollen size analysis: an advanced method to assess somatic and gametophytic ploidy in flowering plants - Nico De Storme; Linda Zamariola; Martin Mau; Timothy F. Sharbel; Danny Geelen (Plant Reproduction, 2013)

Production of a chiral alcohol, 1-(3,4-dihydroxyphenyl) ethanol, by mushroom tyrosinase - Sarah J. Brooks; Jasmina Nikodinovic; Leona Martin; Evelyn M. Doyle; Timothy O’Sullivan; Patrick J. Guiry; Lydie Coulombel; Zhi Li; Kevin E. O’Connor (Biotechnology Letters, 2013)

Biogeographic partitioning of S outhern O cean microorganisms revealed by metagenomics - David Wilkins; Federico M. Lauro; Timothy J. Williams; Matthew Z. Demaere; Mark V. Brown; Jeffrey M. Hoffman; Cynthia Andrews‐Pfannkoch; Jeffrey B. Mcquaid; Martin J. Riddle; Stephen R. Rintoul; Ricardo Cavicchioli (Environmental Microbiology, 2013)
Summary We performed a metagenomic survey (6.6 Gbp of 454 sequence data) of S outhern O cean ( SO ) microorganisms during the austral summer of 2007–2008, examining the genomic signatures of communities across a latitudinal transect from Hobart (44° S ) to the M ertz G lacier, A ntarctica (67° S ). Operational taxonomic units ( OTUs ) of the SAR 11 and SAR 116 clades and the cyanobacterial genera P rochlorococcus and S ynechococcus were strongly overrepresented north of the P olar F ront ( PF ). Conversely, OTUs of the G ammaproteobacterial S ulfur O xidizer‐ EOSA ‐1 ( GSO‐EOSA ‐1) complex, the phyla B acteroidetes and V errucomicrobia and order R hodobacterales were characteristic of waters south of the PF . Functions enriched south of the PF included a range of transporters, sulfur reduction and histidine degradation to glutamate, while branched‐chain amino acid transport, nucleic acid biosynthesis and methionine salvage were overrepresented north of the PF . The taxonomic and functional characteristics suggested a shift of primary production from cyanobacteria in the north to eukaryotic phytoplankton in the south, and reflected the different trophic statuses of the two regions. The study provides a new level of understanding about SO microbial communities, describing the contrasting taxonomic and functional characteristics of microbial assemblages either side of the PF .

Relative contributions of crown and phenological traits to growth of a pseudo-backcross pine family ((slash × loblolly) × slash) and its pure species progenitors - Patricio R. Muñoz Del Valle; Dudley A. Huber; Timothy A. Martin (Tree Genetics & Genomes, 2012)

Detection of alkaloids and carbohydrates by taste receptor cells of the galea of gypsy moth larvae, Lymantria dispar (L.) - Timothy L. Martin; Vonnie D. D. Shields (Arthropod-Plant Interactions, 2012)

An electrophysiological analysis of the effect of phagostimulant mixtures on the responses of a deterrent-sensitive cell of gypsy moth larvae, Lymantria dispar (L.) - Timothy L. Martin; Vonnie D. C. Shields (Arthropod-Plant Interactions, 2012)

Constraining Holocene lake levels and coastal dune activity in the Lake Michigan basin - Timothy G. Fisher; Kelly A. Weyer; Amber M. Boudreau; James M. Martin-Hayden; David E. Krantz; Andy Breckenridge (Journal of Paleolimnology, 2012)

Scenarios for investigating risks to biodiversity - Joachim H. Spangenberg; Alberte Bondeau; Timothy R. Carter; Stefan Fronzek; Jill Jaeger; Kirsti Jylhä; Ingolf Kühn; Ines Omann; Alex Paul; Isabelle Reginster; Mark Rounsevell; Oliver Schweiger; et al. (Global Ecology and Biogeography, 2012)
Aim This paper describes a set of integrative scenarios developed in the ALARM (Assessing LArge‐scale environmental Risks for biodiversity with tested Methods) project. The ultimate aim of ALARM was to develop and test methods and protocols for the assessment of large‐scale environmental risks to biodiversity and to evaluate mitigation options. Scenarios provide a tool for exploring such risks and the policy options to mitigate them; therefore they play a central role within the ALARM project. Methods Three integrative scenarios (liberalization, business as might be usual, sustainability) were developed and illustrated using the econometric model described in a subsequent paper. They are contextualized with projections from climate models and provide the input for model‐based assessments of biodiversity trends. Additionally, three shock scenarios were developed (Gulf Stream collapse, peak oil, pandemic) to demonstrate the limits of linear extrapolation. As these extend beyond model capabilities, they are discussed semi‐quantitatively based on modelling insights. Results Although the policy impacts on biodiversity are different for different pressures, biomes and species groups, some general trends could be identified. An extension of current EU policies will act as a brake on current trends by slowing down the loss of biodiversity in many cases and in most biomes, but it will be capable of neither halting nor of reversing the loss. Liberalization has the effect of accelerating biodiversity loss across the board, with few exceptions. A coherent sustainability scenario is clearly the most effective at preserving biodiversity, but the variant tested here still does not halt losses in all cases. Main conclusions Current EU policies for protecting biodiversity appear to be insufficient to reverse ongoing losses. Coherent sustainability strategies are effective at conserving biodiversity, but in order to assess losses and then reverse them, measures would need to be introduced that extend beyond the steps tested in the ALARM sustainability scenario.

Scenarios as a tool for large‐scale ecological research: experiences and legacy of the ALARM project - JOSEF SETTELE; TIMOTHY R. CARTER; INGOLF KüHN; JOACHIM H. SPANGENBERG; MARTIN T. SYKES (Global Ecology and Biogeography, 2012)

Projecting the future distribution of European potential natural vegetation zones with a generalized, tree species‐based dynamic vegetation model - Thomas Hickler; Katrin Vohland; Jane Feehan; Paul A. Miller; Benjamin Smith; Luis Costa; Thomas Giesecke; Stefan Fronzek; Timothy R. Carter; Wolfgang Cramer; Ingolf Kühn; Martin T. Sykes (Global Ecology and Biogeography, 2012)
Aim To assess the extent to which climate change might cause changes in potential natural vegetation (PNV) across Europe. Location Europe. Method We parameterized a generalized dynamic vegetation model (LPJ‐GUESS) for the most common European tree species, and, for the first time, modelled large‐scale vegetation dynamics using a process‐based model explicitly representing tree species, age cohorts, gap dynamics and biogeochemical cycles in a single framework. For projections, the model was driven with climate scenario data from two atmosphere–ocean general circulation models (AOGCMs), downscaled to 10 × 10′ spatial resolution ( c . 18.5 × 12 km at 50° N). Results At a general level, modelled present‐day PNV corresponded better with an expert reconstruction of the PNV than most earlier plant functional type (PFT)‐based simulations, but at a finer scale the model and the expert map showed substantial discrepancies in some areas. Simulations until 2085 showed considerable successional shifts in vegetation types in most areas: 31–42% of the total area of Europe was projected to be covered by a different vegetation type by the year 2085. In the long term, equilibrium changes are substantially larger: simulations with one climate scenario suggest that 76–80% of the European land surface could exist within another PNV if climate was stabilized by the end of the century and vegetation had unlimited time to achieve equilibrium with the new climate. ‘Hotspots’ of change include arctic and alpine ecosystems, where trees replace tundra in the model, and the transition zone between temperate broad‐leaved and boreal conifer forest. In southern Europe, the model projected widespread shifts from forest to shrublands as a result of drought. Main conclusions The model presents a considerable advance in modelling dynamic changes in natural vegetation across Europe. Climate change might cause substantial changes in PNV across Europe, which should be considered in the management of reserves and forestry.

Comparative analysis of inactivated-state block of N-type (Cav2.2) calcium channels - Timothy A. Vortherms; Andrew M. Swensen; Wende Niforatos; James T. Limberis; Torben R. Neelands; Richard S. Janis; Rama Thimmapaya; Diana L. Donnelly-Roberts; Marian T. Namovic; Di Zhang; C. Brent Putman; Ruth L. Martin; et al. (Inflammation Research, 2011)

Phylogenetic analysis of mitochondrial DNA sequences reveals polyphyly in the goitred gazelle (Gazella subgutturosa) - Timothy Wacher; Torsten Wronski; Robert L. Hammond; Bruce Winney; Mark J. Blacket; Kris J. Hundertmark; Osama B. Mohammed; Sawsan A. Omer; William Macasero; Hannes Lerp; Martin Plath; Christoph Bleidorn (Conservation Genetics, 2011)

Arbuscular mycorrhizas in southeastern Australian processing tomato farm soils - Timothy Richard Cavagnaro; Ashley W. Martin (Plant and Soil, 2011)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Does food supplementation really enhance productivity of breeding birds? - Timothy J. E. Harrison; Jennifer A. Smith; Graham R. Martin; Dan E. Chamberlain; Stuart Bearhop; Gillian N. Robb; S. James Reynolds (Oecologia, 2010)

Twenty-Five Years of Intensive Forest Management with Southern Pines: Important Lessons Learned - Eric J. Jokela; Timothy A. Martin; Jason G. Vogel (Journal of Forestry, 2010)
A commitment to long-term forest research provides the basis and opportunity to understand developmental processes and stand dynamics over an entire rotation. The southeastern United States has undergone a significant evolution in forest management practices over the last 60 years, especially in regard to the intensification of pine plantation silviculture. However, few studies have examined production relationships for an entire rotation. This article reviews results from a rotation-length experiment that tested factorial combinations of understory competition control and sustained fertilizer additions on the productivity and stand dynamics of loblolly (Pinus taeda L.) and slash pine (Pinus elliottii var. elliottii) in north central Florida. After 25 years, fertilizer and competition control treatments increased site index (base age, 25 years) from 64 to 87 ft in loblolly pine and from 75 to 88 ft in slash pine. In addition, these cultural treatments increased total stand stem volume accumulation by 1.8–2.2-fold compared with the control treatments for slash and loblolly pine, respectively; the proportion of volume in high-value product classes such as chip-n-saw (C/S) and sawtimber was also increased in both species (e.g., 39% in C/S and sawtimber in the loblolly pine control treatment versus 74–87% in the fertilizer and/or weed control treatments). Overall, results from this study, as well as others in the region, highlight the overriding importance of soil nutrient supply on long-term productivity of southern pine stands.

Two reciprocally monophyletic mtDNA lineages elucidate the taxonomic status of Mountain gazelles ( Gazella gazella ) - Torsten Wronski; Timothy Wacher; Robert L. Hammond; Bruce Winney; Kris J. Hundertmark; Mark J. Blacket; Osama B. Mohammed; Benito Flores; Sawsan A. Omer; William Macasero; Martin Plath; Ralph Tiedemann; et al. (Systematics and Biodiversity, 2010)

Growing season temperatures limit growth of loblolly pine (Pinus taeda L.) seedlings across a wide geographic transect - Jason E. Nedlo; Timothy A. Martin; James M. Vose; Robert O. Teskey (Trees, 2009)

Trade‐Offs in the Design of Fishery Closures: Management of Silky Shark Bycatch in the Eastern Pacific Ocean Tuna Fishery - JORDAN T. WATSON; TIMOTHY E. ESSINGTON; CLERIDY E. LENNERT‐CODY; MARTIN A. HALL (Conservation Biology, 2009)
Bycatch—the incidental catch of nontarget species—is a principal concern in marine conservation and fisheries management. In the eastern Pacific Ocean tuna fishery, a large fraction of nonmammal bycatch is captured by purse‐seine gear when nets are deployed around floating objects. We examined the spatial distribution of a dominant species in this fishery's bycatch, the apex predator silky shark ( Carcharhinus falciformis ), from 1994 to 2005 to determine whether spatial closures, areas where fishing is prohibited, might effectively reduce the bycatch of this species. We then identified candidate locations for fishery closures that specifically considered the trade‐off between bycatch reduction and the loss of tuna catch and evaluated ancillary conservation benefits to less commonly captured taxa. Smoothed spatial distributions of silky shark bycatch did not indicate persistent small areas of especially high bycatch for any size class of shark over the 12‐year period. Nevertheless, bycatch of small silky sharks (

Alcohol-induced retrograde memory impairment in rats: prevention by caffeine - Michael J. Spinetta; Martin T. Woodlee; Leila M. Feinberg; Chris Stroud; Kellan Schallert; Lawrence K. Cormack; Timothy Schallert (Psychopharmacology, 2008)

Carbon exchange of a mature, naturally regenerated pine forest in north Florida - THOMAS L. POWELL; HENRY L. GHOLZ; KENNETH L. CLARK; GREGORY STARR; WENDELL P. CROPPER; TIMOTHY A. MARTIN (Global Change Biology, 2008)
We used eddy covariance and biomass measurements to quantify the carbon (C) dynamics of a naturally regenerated longleaf pine/slash pine flatwoods ecosystem in north Florida for 4 years, July 2000 to June 2002 and 2004 to 2005, to quantify how forest type, silvicultural intensity and environment influence stand‐level C balance. Precipitation over the study periods ranged from extreme drought (July 2000–June 2002) to above‐average precipitation (2004 and 2005). After photosynthetic photon flux density (PPFD), vapor pressure deficit (VPD) >1.5 kPa and air temperature 2 exchange (NEE day ) and reduced the magnitude of midday CO 2 exchange by >5 μmol CO 2 m −2 s −1 . Analysis of water use efficiency indicated that stomatal closure at VPD>1.5 kPa moderated transpiration similarly in both drought and wet years. Night‐time exchange (NEE night ) was an exponential function of air temperature, with rates further modulated by soil moisture. Estimated annual net ecosystem production (NEP) was remarkably consistent among the four measurement years (range: 158–192 g C m −2 yr −1 ). In comparison, annual ecosystem C assimilation estimates from biomass measurements between 2000 and 2002 ranged from 77 to 136 g C m −2 yr −1 . Understory fluxes accounted for approximately 25–35% of above‐canopy NEE over 24‐h periods, and 85% and 27% of whole‐ecosystem fluxes during night and midday (11:00–15:00 hours) periods, respectively. Concurrent measurements of a nearby intensively managed slash pine plantation showed that annual NEP was three to four times greater than that of the Austin Cary Memorial Forest, highlighting the importance of silviculture and management in regulating stand‐level C budgets.

Inheritance of foliar stable carbon isotope discrimination and third-year height in Pinus taeda clones on contrasting sites in Florida and Georgia - Brian S. Baltunis; Timothy A. Martin; Dudley A. Huber; John M. Davis (Tree Genetics & Genomes, 2008)

Pulmonary adaptations to swim and inspiratory muscle training - Timothy D. Mickleborough; Joel M. Stager; Ken Chatham; Martin R. Lindley; Alina A. Ionescu (European Journal of Applied Physiology, 2008)

Relationships between Human Disturbance and Wildlife Land Use in Urban Habitat Fragments - LISA MARKOVCHICK‐NICHOLLS; HELEN M. REGAN; DOUGLAS H. DEUTSCHMAN; ASTRID WIDYANATA; BARRY MARTIN; LANI NOREKE; TIMOTHY ANN HUNT (Conservation Biology, 2008)
Habitat remnants in urbanized areas typically conserve biodiversity and serve the recreation and urban open‐space needs of human populations. Nevertheless, these goals can be in conflict if human activity negatively affects wildlife. Hence, when considering habitat remnants as conservation refuges it is crucial to understand how human activities and land uses affect wildlife use of those and adjacent areas. We used tracking data (animal tracks and den or bed sites) on 10 animal species and information on human activity and environmental factors associated with anthropogenic disturbance in 12 habitat fragments across San Diego County, California, to examine the relationships among habitat fragment characteristics, human activity, and wildlife presence. There were no significant correlations of species presence and abundance with percent plant cover for all species or with different land‐use intensities for all species, except the opossum (Didelphis virginiana), which preferred areas with intensive development. Woodrats (Neotoma spp.) and cougars (Puma concolor) were associated significantly and positively and significantly and negatively, respectively, with the presence and prominence of utilities. Woodrats were also negatively associated with the presence of horses. Raccoons (Procyon lotor) and coyotes (Canis latrans) were associated significantly and negatively and significantly and positively, respectively, with plant bulk and permanence. Cougars and gray foxes (Urocyon cinereoargenteus) were negatively associated with the presence of roads. Roadrunners (Geococcyx californianus) were positively associated with litter. The only species that had no significant correlations with any of the environmental variables were black‐tailed jackrabbits (Lepus californicus) and mule deer (Odocoileus hemionus). Bobcat tracks were observed more often than gray foxes in the study area and bobcats correlated significantly only with water availability, contrasting with results from other studies. Our results appear to indicate that maintenance of habitat fragments in urban areas is of conservation benefit to some animal species, despite human activity and disturbance, as long as the fragments are large.

Tropical montane forest ecotones: climate gradients, natural disturbance, and vegetation zonation in the Cordillera Central, Dominican Republic - Patrick H. Martin; Ruth E. Sherman; Timothy J. Fahey (Journal of Biogeography, 2007)
Aim We examined relationships between climate–disturbance gradients and patterns of vegetation zonation and ecotones on a subtropical mountain range. Location The study was conducted on the windward slopes of the Cordillera Central, Dominican Republic, where cloud forest appears to shift in a narrow ecotone to monodominant forest of Pinus occidentalis . Methods Climate, disturbance and vegetation data were collected over the elevation range 1100–3100 m and in 50 paired plots along the ecotone. Aerial photographs were georeferenced to a high‐resolution digital elevation model in order to enable the analysis of landscape‐scale patterns of the ecotone. Results A Shipley–Keddy test detected discrete compositional ecotones at 2200 and 2500 m; the distributions of tree species at lower elevations were continuous. The elevation of the ecotone determined with aerial photographs was fairly consistent, namely ± 164 m (SD) over its 124‐km length, but it exhibited significant landscape variation, occurring at a lower elevation in a partially leeward, western zone. The ecotone also occurred significantly lower on ridges than it did in drainage gullies. Ecotone forest structure and composition differed markedly between paired plots. In pine paired plots, the canopy height was 1.7 times higher and the basal area of non‐pine species was 6 times lower than in the cloud forest directly below. Fire evidence was ubiquitous in the pine forest but rare in the abutting cloud forest. Mesoclimate changed discontinuously around the elevation of the ecotone: humidity and cloud formation decreased markedly, and frost frequency increased exponentially. Main conclusions The discreteness of the ecotone was produced primarily by fire. The elevational consistency of the ecotone, however, resulted from the overarching influence of mesoclimate on the elevational patterns of fire occurrence. Declining temperature and precipitation combine with the trade‐wind inversion to create a narrow zone where high‐elevation fires extinguish, enabling fire‐sensitive and fire‐tolerant taxa to abut. Once established, mesotopography and contrasting vegetation physiognomy probably reinforce this boundary through feedbacks on microenvironment and fire likelihood. The prominence of the pine in this study – and of temperate and fire‐tolerant taxa in subtropical montane forests in general – highlights the importance of climate‐disturbance–biogeography interactions in ecotone formation, particularly where fire mediates a dynamic between climate and vegetation.

Projected Changes in Terrestrial Carbon Storage in Europe under Climate and Land-use Change, 1990–2100 - Sönke Zaehle; Alberte Bondeau; Timothy R. Carter; Wolfgang Cramer; Markus Erhard; I. Colin Prentice; I. Reginster; Mark D. A. Rounsevell; Stephen Sitch; Benjamin Smith; Pascalle C. Smith; Martin Sykes (Ecosystems, 2007)

Low stocks of coarse woody debris in a southwest Amazonian forest - Timothy R. Baker; Eurídice N. Honorio Coronado; Oliver L. Phillips; Jim Martin; Geertje M. F. van der Heijden; Michael Garcia; Javier Silva Espejo (Oecologia, 2007)

Effect of a woody (Salix nigra) and an herbaceous (Juncus effusus) macrophyte species on methane dynamics and denitrification - Jamie Smialek; Virginie Bouchard; Becky Lippmann; Martin Quigley; Timothy Granata; Jay Martin; Larry Brown (Wetlands, 2006)

Molecular mechanisms of metastasis - Dave S. B. Hoon; Minoru Kitago; Joseph Kim; Takuji Mori; Adriano Piris; Katherine Szyfelbein; Martin C. Mihm; S. David Nathanson; Timothy P. Padera; Ann F. Chambers; Sharon A. Vantyghem; Ian C. MacDonald; et al. (Cancer and Metastasis Reviews, 2006)

Influence of menstrual cycle phase on pulmonary function in asthmatic athletes - Kristin I. Stanford; Timothy D. Mickleborough; Shahla Ray; Martin R. Lindley; David M. Koceja; Joel M. Stager (European Journal of Applied Physiology, 2006)

Design of a 3D Chirp Sub-bottom Imaging System - Jonathan M. Bull; Martin Gutowski; Justin K. Dix; Timothy J. Henstock; Peter Hogarth; Timothy G. Leighton; Paul R. White (Marine Geophysical Research, 2005)

Time-dependent recovery from the effects of 6-hydroxydopamine lesions of the rat nucleus accumbens on cocaine self-administration and the levels of dopamine in microdialysates - Glen M. Sizemore; Conchita Co; Timothy R. Koves; Thomas J. Martin; James E. Smith (Psychopharmacology, 2004)

The seed ecology of Ascarina lucida : A rare New Zealand tree adapted to disturbance - Timothy J. Martin; John Ogden (New Zealand Journal of Botany, 2002)
Ascarina lucida is rare in the North Island of New Zealand, occurring as small scattered populations. The seed ecology of this species was investigated by laboratory germination of fresh seed, and germination of samples from soil seed banks of two North Island populations. Seed collected from a submontane population had higher germinability (76%) than seed collected from a lowland population (32%). Seed collected from an isolated lowland garden tree had high germinability (82%). A. lucida seeds were abundant in both the surface and basal soil layers, and it was predicted that the species maintains a persistent seed bank for up to c. 8 years. A. lucida was the dominant component of the seed bank at the submontane site. The germination pattern of A. lucida was compared with other woody species in the seed bank and found to have similarities with species that often colonise disturbed sites. The maintenance of a persistent seed bank, coupled with the long period of time over which fresh seed germinates, gives this species flexibility in the timing of germination. Overall, the results indicate that the species is adapted to disturbed environments.

Ideotype Development in Southern Pines: Rationale and Strategies for Overcoming Scale-Related Obstacles - Timothy A. Martin; Kurt H. Johnsen; Timothy L. White (Forest Science, 2001)
Indirect genetic selection for early growth and disease resistance of southern pines has proven remarkably successful over the past several decades. However, several benefits could be derived for southern pine breeding programs by incorporating ideotypes, conceptual models which explicitly describe plant phenotypic characteristics that are hypothesized to produce greater yield. The potential benefits of using ideotypes include improvement in trait heritabilities and genetic correlations, higher genetic gain in diverse silvicultural environments, guidance for developing mating designs, and provision of a framework for synthesis of tree production physiology knowledge. There are numerous obstacles to the development of ideotypes for southern pines, most of them related to the difficulty of linking traits and processes that operate at small spatial and temporal scales (e.g., tree crown morphological traits or leaf net photosynthesis) with outputs that occur at large spatial and temporal scales (e.g., stand-level, rotation-age stem biomass yield). Fortunately, as we enter the 21st century, several relevant advances are converging that bode well for overcoming these obstacles. These advances relate to improvements and developments of process modeling, advances in technologies that permit measures of component processes at relevant scales, the likely future importance of intensive clonal forestry, and the movement toward large-scale genetic block plot experiments. FOR. Sci. 47(1):21–28.

Hydrogeologic modeling of the genesis of carbonate-hosted lead-zinc ores - Grant Garven; Martin S. Appold; Vera I. Toptygina; Timothy J. Hazlett (Hydrogeology Journal, 1999)

Induction of hepatic mrp2 ( cmrp / cmoat ) gene expression in nonhuman primates treated with rifampicin or tamoxifen - Hans-Martin Kauffmann; Dietrich Keppler; Timothy W. Gant; Dieter Schrenk (Archives of Toxicology, 1998)

A drop technique for ¯atworm chromosome preparation for light microscopy and high-resolution scanning electron microscopy - Dunja K. Lamatsch; Timothy F. Sharbel; Regina Martin; Cornelia Bock (Chromosome Research, 1998)

Hereditary neuralgic amyotrophy: evidence for genetic homogeneity and mapping to chromosome 17q25 - Joan E. Pellegrino; Roberta A. V. George; Jacquelyn Biegel; Martin R. Farlow; Kathy Gardner; Judy Caress; Mark J. Brown; Timothy R. Rebbeck; Thomas D. Bird; P. F. Chance (Human Genetics, 1997)

Seasonal distribution of sympagic amphipods near Chesterfield Inlet, N.W.T., Canada - Timothy D. Siferd; Harold E. Welch; Martin A. Bergmann; Martin F. Curtis (Polar Biology, 1997)

Acetylator genotype-dependent N-acetylation of arylamines in vivo and in vitro by hepatic and extrahepatic organ cytosols of Syrian hamsters congenic at the polymorphic acetyltransferase locus - David W. Hein; Timothy D. Rustan; William J. Martin; Kyle D. Bucher; Linda S. Miller; Erik J. Furman (Archives of Toxicology, 1992)